Resin composition, cured product, resin sheet, circuit substrate, semiconductor chip package, semiconductor device, and structure
Patent Information
- Application Number
- CN202111525822.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-16
- Filing Date
- 2021-12-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-12-14
AI Technical Summary
In the semiconductor chip packaging process, it is difficult to form small openings in the photosensitive resin composition, resulting in poor wiring. Existing technologies cannot simultaneously improve resolution, mechanical properties, and electrical properties.
A resin composition comprising epoxy resin, anhydride-based curing agent, amine-based curing agent or phenol-based curing agent and inorganic filler is used to improve the resolution of the photosensitive resin composition by controlling the surface roughness and thickness uniformity of the cured layer of the resin composition.
The resolution of the photosensitive resin composition layer is improved, the residue at the opening is reduced, and the reliability and accuracy of the wiring are ensured.
Smart Images

Figure CN114634683B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to resin compositions comprising epoxy resin. Further, this invention relates to cured products, resin sheets, circuit boards, semiconductor chip packages, semiconductor devices, and structures obtained using the resin compositions. Background Technology
[0002] In recent years, with the increasing demand for small, high-performance electronic devices such as smartphones and tablets, the sealing materials used for semiconductor chip packaging in these small electronic devices have also been required to be further enhanced in functionality. As such sealing materials, materials formed by curing resin compositions are known (Patent Documents 1-3).
[0003] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2004-137370 Patent Document 2: Japanese Patent Application Publication No. 2012-188555 Patent document 3: Japanese Patent Application Publication No. 2016-74920. Summary of the Invention
[0004] The problem that the invention aims to solve In the manufacture of semiconductor chip packages, a cured layer is sometimes formed on a circuit board using a cured resin composition as an insulating or sealing layer. Furthermore, sometimes a photosensitive resin composition is used as a resist on this cured layer to form wiring such as a redistribution layer, through which the conductor layer of the circuit board is electrically connected to the semiconductor chip.
[0005] In the formation of wiring using a photosensitive resin composition, the following steps are generally performed: forming a layer of the photosensitive resin composition; exposing the layer of the photosensitive resin composition through a mask to form a latent image of the wiring pattern; removing the portion of the photosensitive resin composition on which the latent image is formed by development; and forming wiring in the portion where the photosensitive resin composition has been removed. In the following description, the portion where the photosensitive resin composition has been removed is sometimes referred to as an "opening portion". Therefore, the size of the opening portion where the photosensitive resin composition has been removed by development can correspond to the size of the wiring. For example, by reducing the size of the opening portion, the linewidth of the wiring can be reduced. In recent years, in order to achieve wiring miniaturization, attempts have been made to reduce the size of the opening portion of the photosensitive resin composition layer.
[0006] However, when the opening is small, it becomes more difficult to form the opening as intended. For example, in a portion of the opening corresponding to the wiring pattern, residue may sometimes form in the opening if the photosensitive resin composition is not sufficiently removed. This residue can be a clump of photosensitive resin composition that has not been removed. When this residue is present in a portion of the opening, proper wiring cannot be formed, which can lead to poor conductivity.
[0007] Therefore, attempts were made to improve the photosensitive resin composition to enhance resolution. "Resolution" refers to the property of forming small openings in the layers of the photosensitive resin composition. However, improving resolution solely through modification of the photosensitive resin composition is challenging. For example, in manufacturing semiconductor chip packages by mounting semiconductor chips on a circuit board, the photosensitive resin composition, after being used as a photoresist, can be cured as an insulating or sealing layer within the semiconductor chip package as needed. Therefore, in such cases, the photosensitive resin composition requires not only excellent resolution but also superior mechanical and electrical properties. Consequently, improvements to the photosensitive resin composition sometimes involve constraints related to factors other than resolution. Based on these considerations, the inventors explored methods other than modifying the photosensitive resin composition to improve resolution.
[0008] The inventors conducted research and found that when a cured layer is formed using a cured resin composition comprising an epoxy resin, at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and an inorganic filler, the photosensitive resin composition formed on the cured layer generally has poor resolution. Therefore, the inventors attempted to improve the resolution of the photosensitive resin composition layer formed on the cured layer by modifying the resin composition used as the material of the cured layer, rather than modifying the photosensitive resin composition itself.
[0009] The present invention was created in view of the above-mentioned problems, and its object is to provide: a resin composition comprising: (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents and phenolic curing agents, and (C) an inorganic filler material, wherein the resin composition can improve the resolution of a layer of photosensitive resin composition formed on a cured layer of the resin composition; a cured product using the resin composition, a resin sheet, a circuit board, a semiconductor chip package and a semiconductor device; and a structure comprising: a cured layer formed using a cured product of a resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents and phenolic curing agents, and (C) an inorganic filler material, and a layer of photosensitive resin composition formed on the cured product layer, wherein the resolution of the layer of photosensitive resin composition is excellent.
[0010] Solution for solving the problem The inventors have conducted diligent research to solve the aforementioned problems. As a result, the inventors discovered that in a specific evaluation test of forming a layer of photosensitive resin composition on the polished surface of a cured resin composition, if the surface roughness of the photosensitive resin composition layer is within a specific range and the difference between the maximum and minimum thickness (TTV) of the photosensitive resin composition layer is within a specific range, the aforementioned problems can be solved, thereby completing the present invention.
[0011] That is, the present invention includes the following: [1] A resin composition comprising: (A) epoxy resin, (B) at least one curing agent selected from anhydride-based, amine-based, and phenol-based curing agents, and (C) inorganic filler material, wherein... In the case of an evaluation test in which a test layer was formed on the polished surface of a cured specimen of the resin composition using the test composition, The arithmetic mean roughness Ra of the surface of the test layer on the opposite side of the polished surface is greater than 10 nm and less than 500 nm. The difference between the maximum and minimum thickness of the test layer, TTV, is greater than 0.2 μm and less than 8 μm. The polished surface is formed by performing the following steps: A layer of the resin composition is formed on a silicon wafer by compression molding. The resin composition is heat-cured to obtain the cured sample, and The cured sample is ground to obtain the ground surface; The test layer is formed by performing the following steps: The cured sample was cut into a circle, and the test composition was spin-coated onto the polished surface of the cured sample. The sample was then heated to form a layer of the test composition. The test layer is obtained by thermally curing the layer of the test composition. The test composition is selected from at least one of negative photosensitive resin compositions and positive photosensitive resin compositions; [2] The resin composition according to [1], wherein (A) the epoxy resin comprises a naphthalene-type epoxy resin; [3] According to the resin composition of [1] or [2], wherein, relative to 100% by mass of the non-volatile components in the resin composition, the amount of (C) inorganic filler is 60% by mass or more; [4] The resin composition according to any one of [1] to [3], wherein the resin composition comprises a silane coupling agent; [5] The resin composition according to any one of [1] to [4], wherein the tensile modulus of the cured product obtained by thermosetting the resin composition at 150°C for 1 hour is 30 GPa or less; [6] The resin composition according to any one of [1] to [5] is used to form an insulating layer for semiconductor chip packaging; [7] The resin composition according to any one of [1] to [6], wherein, In the evaluation test, the polished surface is formed by performing the following steps: A layer of the resin composition with a thickness of 300 μm was formed on a 12-inch silicon wafer by compression molding under conditions of 130°C, 6 MPa, and 10 minutes of curing time. The resin composition was thermally cured at 150°C for 1 hour to obtain the cured sample, and the cured sample was ground 30 μm in the thickness direction to obtain the ground surface with an arithmetic mean roughness of 10 nm to 300 nm. [8] The resin composition according to any one of [1] to [7], wherein, In the evaluation test, the test layer is formed by performing the following steps: The cured sample was cut into a 4-inch circle. The test composition is spin-coated onto the polished surface of the cured sample and heated at 120°C for 5 minutes to form a layer of the test composition. The layer of the test composition is then heat-cured at 250°C for 2 hours to obtain the test layer with a central thickness of 8 μm. [9] The resin composition according to any one of [1] to [8], wherein, The negative photosensitive resin composition is a composition with a viscosity of 35 poise obtained by dissolving 50 parts by weight of the first polymer, 50 parts by weight of the second polymer, 2 parts by weight of the compound shown in formula (1) below, 8 parts by weight of tetraethylene glycol dimethacrylate, 0.05 parts by weight of 2-nitroso-1-naphthol, 4 parts by weight of N-phenyldiethanolamine, 0.5 parts by weight of N-(3-(triethoxysilyl)propyl)o-carbamoylbenzoic acid, and 0.5 parts by weight of benzophenone-3,3'-bis(N-(3-triethoxysilyl)propionamide)-4,4'-dicarboxylic acid in a mixed solvent (weight ratio 8:2) formed by N-methylpyrrolidone and ethyl lactate. The first polymer is a polymer with a weight average molecular weight of 18,000 to 25,000, obtained by reacting 155.1 parts by mass of 4,4'-oxophthalic dianhydride with 134.0 parts by mass of 2-hydroxyethyl methacrylate with 206.3 parts by mass of dicyclohexylcarbodiimide, and further reacting with 93.0 parts by mass of 4,4'-diaminodiphenyl ether; the second polymer is a polymer with a weight average molecular weight of 18,000 to 25,000, obtained by reacting 147.1 parts by mass of 3,3',4'-biphenyltetracarboxylic dianhydride with 134.0 parts by mass of 2-hydroxyethyl methacrylate with 206.3 parts by mass of dicyclohexylcarbodiimide, and further reacting with 93.0 parts by mass of 4,4'-diaminodiphenyl ether. The positive photosensitive resin composition is a mixture of 100 parts by weight of the third polymer, 15 parts by weight of hexamethoxymethyl melamine, 11 parts by weight of 1-naphthoquinone-2-diazido-5-sulfonate, and 200 parts by weight of γ-butyrolactone. The third polymer is a polymer having a weight-average molecular weight of 10,000 to 50,000 and a dispersion of 2.0. This third polymer is obtained by reacting 13.92 parts by mass of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane with 10.69 parts by mass of dodecanedioic acid dichloride. [Chemical Formula 1]
[10] A cured product, which is a cured product of the resin composition described in any one of [1] to [9];
[11] A resin sheet comprising: A support body, and a resin composition layer comprising any one of [1] to [9] disposed on the support body;
[12] A circuit board comprising a cured product of the resin composition described in any one of [1] to [9];
[13] A semiconductor chip package comprising a cured product of the resin composition described in any one of [1] to [9];
[14] A semiconductor device comprising the semiconductor chip package described in
[13] ;
[15] A structure comprising: A cured layer formed from a cured thermosetting resin composition, and a layer of photosensitive resin composition formed in a manner that is in contact with the surface of the cured layer; The thermosetting resin composition comprises (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents and phenol-based curing agents, and (C) an inorganic filler. The arithmetic mean roughness Ra of the surface on the opposite side of the cured layer of the layer obtained by curing the layer of the photosensitive resin composition is 10 nm or more and less than 500 nm, and the difference between the maximum thickness and the minimum thickness TTV of the layer obtained by curing the layer of the photosensitive resin composition is 0.2 μm or more and less than 8 μm.
[0012] The effects of the invention According to the present invention, a resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and (C) an inorganic filler material can be provided, the resin composition improving the resolution of a layer of photosensitive resin composition formed on a cured layer of the resin composition; a cured product using the resin composition, a resin sheet, a circuit board, a semiconductor chip package, and a semiconductor device; and a structure comprising: a cured layer formed from a cured product of a resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and (C) an inorganic filler material, and a layer of photosensitive resin composition formed on the cured layer, the layer of photosensitive resin composition having excellent resolution.
[0013] Brief description of the attached diagram Figure 1 It is a schematic cross-sectional view of a sample manufactured through a specific evaluation test; Figure 2 This is a schematic cross-sectional view of a fan-out type WLP, which is an example of a semiconductor chip package according to one embodiment of the present invention. Detailed Implementation
[0014] The following describes in detail embodiments and examples of the present invention. However, the present invention is not limited to the embodiments and examples described below, and can be implemented by any modifications without departing from the scope of the claims and their equivalents.
[0015] [1. Overview of the Resin Composition] One embodiment of the present invention relates to a resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and (C) an inorganic filler. Hereinafter, to distinguish it from a photosensitive resin composition that can be formed on a cured layer of this resin composition, the resin composition according to this embodiment, comprising components (A) to (C), is sometimes referred to as a "specific resin composition". Specific resin compositions are generally thermosetting resin compositions that are heat-curable. When an evaluation test is conducted on the polished surface of a cured specimen of the specific resin composition to form a test layer using the test composition, the specific resin composition satisfies both of the following conditions (i) and (ii). Hereinafter, the evaluation test is sometimes referred to as a "specific evaluation test". (i) The arithmetic mean roughness Ra of the surface of the test layer on the opposite side of the grinding surface is greater than 10 nm and less than 500 nm; (ii) The difference between the maximum and minimum thickness of the test layer, TTV, is greater than 0.2 μm and less than 8 μm.
[0016] Condition (i) is detailed below. Specifically, the arithmetic mean roughness Ra of the surface of the test layer opposite to the polished surface is typically less than 500 nm, preferably less than 450 nm, and more preferably less than 400 nm. Furthermore, the arithmetic mean roughness Ra is typically 10 nm or more, for example, 12 nm or more, 14 nm or more, etc. The arithmetic mean roughness is specified by JIS B 0601.
[0017] Condition (ii) is detailed below. Specifically, the difference between the maximum and minimum thickness of the test layer, TTV, is typically 8 μm or less, preferably 7 μm or less, and more preferably 6 μm or less. Furthermore, the TTV is typically 0.2 μm or more, for example, 0.3 μm or more, 0.4 μm or more, etc.
[0018] The specific evaluation test for a specific resin composition refers to a test in which a test layer is formed on the polished surface of a cured specimen of the specific resin composition using the test composition. The cured specimen refers to the cured product of the specific resin composition for testing. Furthermore, the test composition is a photosensitive resin composition used to evaluate the specific resin composition, and at least one selected from negative and positive photosensitive resin compositions may be used. In the following description, the negative photosensitive resin composition used as the test composition is sometimes referred to as the "first specific composition," and the positive photosensitive resin composition used as the test composition is sometimes referred to as the "second specific composition."
[0019] In specific evaluation tests, the polished surface is formed by performing the following steps sequentially: Layers of a specific resin composition are formed on a silicon wafer by compression molding. Cured samples are obtained by thermally curing a specific resin composition into layers, and The cured sample is ground to obtain a ground surface.
[0020] A 12-inch silicon wafer can be used as the silicon wafer. Furthermore, the thickness of the layer of the specific resin composition formed on this silicon wafer can be 300 μm. The compression molding is performed at a temperature of 130°C, a pressure of 6 MPa, and a curing time of 10 minutes. Furthermore, the thermosetting of the layer of the specific resin composition is performed at 150°C for 1 hour. Further, the cured sample is ground by grinding the cured sample 30 μm in the thickness direction. This grinding is typically performed using a grinder. A DISCO "DAG810" grinder can be used. This grinder is a cutting-type grinder using a φ200 mm diamond grinding wheel. Furthermore, the grinding is performed to obtain a ground surface with a specific surface roughness. Specifically, the arithmetic mean roughness of the ground surface is typically 10 nm to 300 nm. Therefore, in specific evaluation tests, the polished surface is usually formed by performing the following steps: forming a layer of a specific resin composition with a thickness of 300 μm on a 12-inch silicon wafer by compression molding at a temperature of 130°C, a pressure of 6 MPa, and a curing time of 10 minutes; thermally curing the layer of the specific resin composition at 150°C for 1 hour to obtain a cured sample; and polishing the cured sample 30 μm along the thickness direction to obtain a polished surface with an arithmetic mean roughness of 10 nm to 300 nm.
[0021] Furthermore, in specific evaluation tests, the test layer is formed by sequentially performing the following procedures: The cured sample with the polished surface was cut into a circle. The test composition is spin-coated onto the polished surface of the cured sample and heated to form a layer of the test composition. The layer of the test composition is then thermally cured to obtain the test layer.
[0022] The cured specimen can be cut to form a 4-inch circle. Here, "4-inch circle" means that the cured specimen is a circle with a diameter of 4 inches when viewed from the thickness direction. Furthermore, the spin coating of the test composition onto the polished surface can be performed under conditions that result in a test layer with a central thickness of 8 μm. Typically, the specific spin coating speed is set within a range of 1000 rpm to 3000 rpm, and a test layer with a central thickness of 8 μm is obtained after heat curing. Furthermore, the amount of test composition spin-coated can be adjusted to obtain a test layer with a central thickness of 8 μm. The "center" of the test layer refers to the center of the test layer when viewed from the thickness direction. Furthermore, the heating conditions after spin coating the test composition are typically 120°C for 5 minutes. Further, the heat curing conditions for the test composition layer are typically 250°C for 2 hours. Therefore, in specific evaluation tests, the test layer is typically formed by performing the following steps: cutting the cured sample into a 4-inch circle; spin-coating the test composition onto the polished surface of the cured sample and heating it at 120°C for 5 minutes to form a layer of the test composition; and thermally curing the layer of the test composition at 250°C for 2 hours to obtain the test layer with a central thickness of 8 μm.
[0023] Figure 1 This is a schematic cross-sectional view of sample 1 manufactured through the specific evaluation test described above. For example... Figure 1 As shown, a sample 1 was obtained by performing a specific evaluation test, comprising a silicon wafer 10, a cured sample 20 formed on the surface 10U of the silicon wafer 10, and a test layer 30 formed on the polished surface 20U of the cured sample 20. Condition (i) indicates that the surface 30U of the test layer 30 opposite to the polished surface 20U has an arithmetic mean roughness Ra within a specific range. Furthermore, condition (ii) indicates that the difference between the maximum and minimum thickness TTV of the test layer 30 is within a specific range. Regarding TTV, the thickness of the test layer can be measured at 15 measurement points, including the center and ends of the wafer, and the difference between the maximum and minimum values of these measured thicknesses is used to determine the result.
[0024] The test composition used in the specific evaluation test, as described above, is selected from at least one of a first specific composition as a negative photosensitive resin composition and a second specific composition as a positive photosensitive resin composition.
[0025] The first specific composition is obtained by dissolving 50 parts by weight of a first polymer, 50 parts by weight of a second polymer, 2 parts by weight of a compound represented by formula (1) below, 8 parts by weight of tetraethylene glycol dimethacrylate, 0.05 parts by weight of 2-nitroso-1-naphthol, 4 parts by weight of N-phenyldiethanolamine, 0.5 parts by weight of N-(3-(triethoxysilyl)propyl)o-carbamoylbenzoic acid, and 0.5 parts by weight of benzophenone-3,3'-bis(N-(3-triethoxysilyl)propionamide)-4,4'-dicarboxylic acid in a mixed solvent formed of N-methylpyrrolidone and ethyl lactate (weight ratio of N-methylpyrrolidone:ethyl lactate = 8:2). The amount of mixed solvent is adjusted so that the viscosity of the first specific composition at 23°C is 35 poise. The viscosity of the first specific composition can be measured using an E-type viscometer (Toki Sangyo Co., Ltd. "RE-80U") under conditions of a 1°34'xR24 rotor, 25°C, and a rotation speed of 5 rpm.
[0026] [Chemical Formula 2]
[0027] The first polymer is a polymer with a weight average molecular weight of 18,000 to 25,000 obtained by reacting 155.1 parts by mass of 4,4'-oxophthalic dianhydride with 134.0 parts by mass of 2-hydroxyethyl methacrylate (HEMA) with 206.3 parts by mass of dicyclohexylcarbodiimide (DCC), and then with 93.0 parts by mass of 4,4'-diaminodiphenyl ether (DADPE).
[0028] In detail, the first polymer can be a polymer with a weight-average molecular weight of 18,000 to 25,000 obtained by sequentially performing the following steps: 155.1 g of 4,4'-oxophthalic dianhydride, 134.0 g of 2-hydroxyethyl methacrylate, and 400 ml of γ-butyrolactone were mixed to obtain a first liquid. While stirring the first liquid at 23°C (room temperature), 79.1 g of pyridine was added to the first liquid to obtain a second liquid. The second liquid is exothermic (heat-generating). After the second liquid has finished releasing heat, cool it to 23°C and let it stand for 16 hours. While ice-cooled and stirring, a dicyclohexylcarbodiimide solution (206.3 g dissolved in 180 ml of γ-butyrolactone) was added to the second liquid over 40 minutes to obtain the third liquid. While stirring, add the suspension of 93.0 g of 4,4'-diaminodiphenyl ether in 350 ml of γ-butyrolactone to the third liquid over 60 minutes to obtain the fourth liquid. The fourth liquid was stirred at 23°C for 2 hours. Add 30 ml of ethanol to the fourth liquid and stir for 1 hour to obtain the fifth liquid. Add 400 ml of γ-butyrolactone to the fifth liquid to obtain the sixth liquid. The sixth liquid was filtered to obtain the seventh liquid. The seventh liquid was added to 3 liters of ethanol to obtain the first precipitate. The first precipitate was dissolved in 1.5 liters of tetrahydrofuran to obtain the eighth liquid, and The eighth liquid was added dropwise to 28 liters of water, causing the first polymer to precipitate.
[0029] The second polymer is a polymer with a weight average molecular weight of 18,000 to 25,000 obtained by reacting 147.1 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride with 134.0 parts by mass of 2-hydroxyethyl methacrylate, with 206.3 parts by mass of dicyclohexylcarbodiimide, and then with 93.0 parts by mass of 4,4'-diaminodiphenyl ether.
[0030] In detail, the second polymer can be a polymer with a weight-average molecular weight of 18,000 to 25,000 obtained by sequentially performing the following steps: 147.1 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 134.0 g of 2-hydroxyethyl methacrylate, and 400 ml of γ-butyrolactone were mixed to obtain a ninth liquid. While stirring the ninth liquid at 23°C, 79.1 g of pyridine was added to the ninth liquid to obtain a tenth liquid. The tenth liquid was exothermic. After the exothermic reaction of the tenth liquid is complete, cool it to 23°C and let it stand for 16 hours. Under ice cooling, while stirring, a dicyclohexylcarbodiimide solution (206.3 g dissolved in 180 ml of γ-butyrolactone) was added to the tenth liquid over 40 minutes to obtain the eleventh liquid. While stirring, add the suspension of 93.0 g of 4,4'-diaminodiphenyl ether in 350 ml of γ-butyrolactone to the eleventh liquid over 60 minutes to obtain the twelfth liquid. The twelfth liquid was stirred at 23°C for 2 hours. Add 30 ml of ethanol to the twelfth liquid and stir for 1 hour to obtain the thirteenth liquid. Add 400 ml of γ-butyrolactone to the thirteenth solution to obtain the fourteenth solution. Filter the fourteenth liquid to obtain the fifteenth liquid. The fifteenth liquid was added to 3 liters of ethanol to obtain the second precipitate. The second precipitate was dissolved in 1.5 liters of tetrahydrofuran to obtain the sixteenth liquid, and The sixteenth liquid was added dropwise to 28 liters of water, causing the second polymer to precipitate.
[0031] The second specific composition is a mixture of 100 parts by weight of the third polymer, 15 parts by weight of hexamethoxymethyl melamine as shown in formula (2) below, 11 parts by weight of 1-naphthoquinone-2-diazido-5-sulfonate as a photosensitizer as shown in formula (3) below, and 200 parts by weight of γ-butyrolactone. Hexamethoxymethyl melamine can be "CYMEL300" manufactured by Allnex. Furthermore, 1-naphthoquinone-2-diazido-5-sulfonate can be "TPPA528" manufactured by Daito Chemix.
[0032] [Chemical Formula 3]
[0033] [Chemical Formula 4]
[0034] The third polymer is a polymer with a weight-average molecular weight of 10,000–50,000 and a dispersibility of 2.0, obtained by reacting 13.92 parts by mass of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane with 10.69 parts by mass of dodecanoic acid dichloro. The dispersibility is expressed as a ratio Mw / Mn. Mw represents the weight-average molecular weight, and Mn represents the number-average molecular weight.
[0035] Specifically, the third polymer can be a polymer having a weight-average molecular weight of 10,000 to 50,000 and a dispersion (Mw / Mn) of 2.0, obtained by sequentially performing the following steps: Add 13.92 g (38 mmol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane to 60 g of N-methylpyrrolidone, stir to dissolve, and obtain the seventeenth liquid. While maintaining the seventeenth liquid at 0℃~5℃, 10.69g (40mmol) of dodecanoic acid dichloride was added dropwise to the seventeenth liquid over 10 minutes, and the mixture was stirred for 60 minutes to obtain the eighteenth liquid. When the eighteenth liquid is added to 3 liters of water, a precipitate is produced. The precipitate was washed with pure water to obtain the third polymer.
[0036] The weight-average molecular weight Mw and number-average molecular weight Mn can be obtained by gel permeation chromatography (GPC) using standard polystyrene.
[0037] A specific resin composition that satisfies conditions (i) and (ii) above can improve the resolution of a layer of photosensitive resin composition formed on a cured layer of that specific resin composition. The inventors conjecture as follows that a configuration can improve resolution in this way. However, the scope of the present invention is not limited to the configuration described below.
[0038] For a layer of photosensitive resin composition formed on a cured layer of an existing resin composition, its surface roughness is sometimes high. When the roughness is high, light entering the layer of photosensitive resin composition during exposure can produce undesirable refraction, diffraction, or reflection on its surface. As a result, the light focus shifts, and the focal point may deviate from the intended position. In the areas where the focus is shifted, exposure may become insufficient, thus leaving residue after development.
[0039] Furthermore, the thickness of the photosensitive resin composition layer formed on the cured layer of conventional resin compositions is sometimes uneven. When such thickness is uneven, the depth of focus required for proper exposure can differ between the thicker and thinner portions of the photosensitive resin composition layer. This results in a deviation in the appropriate depth of focus, creating areas in the photosensitive resin composition layer where exposure based on the appropriate depth of focus is impossible. Consequently, exposure may be insufficient in these areas, leaving residue after development.
[0040] When the opening of the photosensitive resin composition is small and needs to be removed by exposure and development, there is a possibility that the opening may become clogged with residue. Moreover, if the opening is clogged with residue in this way, it will become difficult to form the intended wiring in that opening.
[0041] In contrast, in this embodiment, instead of adjusting the composition of the photosensitive resin composition layer, the surface roughness and thickness uniformity of the photosensitive resin composition layer are improved by using the material of the cured layer, which serves as the substrate of the layer, i.e., a specific resin composition. Specifically, in this embodiment, a specific resin composition is provided in which the test layer satisfies conditions (i) and (ii) in a specific evaluation test using a test composition that is a general photosensitive resin composition. Condition (i) indicates that the surface roughness of the photosensitive resin composition layer can be reduced. Furthermore, condition (ii) indicates that the thickness uniformity of the photosensitive resin composition layer can be improved. The specific resin composition of this embodiment, which can form a layer (test layer) with low surface roughness and uniform thickness using a test composition that is a general photosensitive resin composition, can also produce a layer of photosensitive resin composition with low surface roughness and uniform thickness even when using a photosensitive composition other than the test composition. Therefore, as described above, focus shift of the light used for exposure or deviation of the appropriate depth of focus can be suppressed. Therefore, appropriate exposure as expected can be performed, thereby suppressing the generation of residue. Therefore, small openings can be formed, which can improve resolution.
[0042] According to the inventors' research, existing resin compositions comprising epoxy resin, at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and inorganic filler materials are prone to producing residues at the openings described above. Furthermore, the inventors' research has determined that residues are particularly prone to form in existing resin compositions, especially those with a high amount of inorganic filler material and those with a low modulus of elasticity in the cured product. Therefore, from the viewpoint of fully utilizing the improved resolution, it is preferable that a specific resin composition comprising (A) epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and (C) inorganic filler material satisfies conditions (i) and (ii). More preferably, a specific resin composition with a high amount of inorganic filler material and a specific resin composition with a low modulus of elasticity in the cured product satisfy conditions (i) and (ii).
[0043] -Elastic modulus- As a method for obtaining a specific resin composition that fully satisfies the above conditions (i) and (ii), one example is a method of adjusting the composition of the specific resin composition to obtain a cured product having an elastic modulus within a specific range. Specifically, one example is a method of adjusting the composition of the specific resin composition so that the cured product obtained by thermosetting the specific resin composition at 150°C for 1 hour has a tensile elastic modulus within a specific range. The range of tensile elastic modulus of the cured product is preferably 7 GPa or more, more preferably 8 GPa or more, and particularly preferably 9 GPa or more. There is no particular upper limit. However, there is currently a tendency for poor resolution in resin compositions that can produce cured products with low tensile elastic modulus. Therefore, for such resin compositions where resolution improvement is currently particularly difficult, from the viewpoint of improving its resolution and making full use of this embodiment, the tensile elastic modulus of the cured product of the specific resin composition is preferably 30 GPa or less, more preferably 27 GPa or less, and particularly preferably 25 GPa or less.
[0044] The tensile modulus of elasticity of the cured product of a particular resin composition can be determined by the method described in the examples below.
[0045] Particles of the inorganic filler material may detach from the surface of the cured layer of the resin composition containing the inorganic filler material. Particularly in the case of abrasive curing, the inorganic filler material particles tend to detach easily from the abrasive surface due to the force applied during abrasion. Assuming that the inorganic filler material particles detach from the surface of the cured layer, a depression may form as a trace of detachment. With such depressions, the surface of the photosensitive resin composition layer formed on the surface of the cured layer may become rough, or the thickness of the photosensitive resin composition layer may become uneven. In contrast, when the elastic modulus of the cured resin composition is within the aforementioned range, the resin can firmly retain the inorganic filler material particles (C), thus suppressing the detachment of the inorganic filler material particles (C). Therefore, conditions (i) and (ii) can be sufficiently satisfied.
[0046] Generally, the more inorganic filler material in a resin composition, the greater the frequency of particle detachment of the inorganic filler material. Therefore, the specific elastic modulus of the cured product of a particular resin composition is preferably set according to the amount of (C) inorganic filler material particles. Specifically, the ratio of (C) inorganic filler material to 100% by mass of the non-volatile components of the particular resin composition is set as R(C) [mass%], and the tensile elastic modulus of the cured product of the particular resin composition is set as T. M [GPa]. In this case, the ratio R(C) / T is... MIdeally, the concentration should be below 8.0% (mass) / GPa; more preferably, below 7.0% (mass) / GPa; and especially preferably, below 6.5% (mass) / GPa. The lower limit is preferably above 2.0% (mass) / GPa, for example, above 2.5% (mass) / GPa or above 3.0% (mass) / GPa. Ratio R(C) / T M When within the range described, the detachment of particles of (C) inorganic filler material can be effectively suppressed. Therefore, specific resin compositions that fully satisfy conditions (i) and (ii) can usually be obtained, resulting in effective improvement of resolution.
[0047] -Surface free energy- As another method for obtaining a specific resin composition that fully satisfies conditions (i) and (ii) above, one example is a method of adjusting the composition of the specific resin composition to obtain a cured product having a specific range of surface free energy. Specifically, one example is a method of adjusting the composition of the specific resin composition so that the cured product obtained by thermosetting the specific resin composition at 150°C for 1 hour has a specific range of surface free energy. The preferred range of surface free energy of the cured product is 25 mJ / m². 2 The above is better, ideally 30 mJ / m 2 The above, especially ideally 35 mJ / m 2 That's all. There is no particular upper limit. However, from the viewpoint of forming a thick layer of photosensitive resin composition on the cured layer, the surface free energy of the cured material is preferably 200 mJ / m. 2 Below, 150 mJ / m is better. 2 The following is particularly good, with 100 mJ / m 2 the following.
[0048] The surface free energy of the cured resin composition can be determined by the method described in the examples described later. In the examples described later, the surface free energy is determined based on Kitazaki Hata's theory. In Kitazaki Hata's theory, the following equation (4) holds. (γ S d ·γ L d ) 1 / 2 +(γ S p ·γ L p ) 1 / 2 +(γ S h ·γ L h ) 1 / 2 ={γ L (1+cosθ) / 2 (4) Where, γL γ represents the surface free energy of a liquid. L d γ L p and γ L h These represent the dispersion component, polar component, and hydrogen bonding component of the surface free energy of the liquid, respectively. θ represents the contact angle of the liquid relative to the solid. γ S d γ S p and γ S h These represent the dispersion component, polar component, and hydrogen bond component of the surface free energy of a solid, respectively.
[0049] Therefore, prepare the surface free energy γ L and its dispersed component γ L d polar component γ L p and hydrogen bond component γ L h Three known liquids (e.g., water, diiodomethane, and n-hexadecane) were used. The contact angles of each liquid relative to the solidified material were measured. Substituting the measured contact angles into equation (4), the dispersion component γ of the surface free energy of the solidified material was obtained by solving the simultaneous equations (system of equations). S d polar component γ S p and hydrogen bond component γ S h Therefore, the surface free energy E of the solidified material can be obtained as the sum of these components using the following equation (5). E = γ S d +γ S p +γ S h (5).
[0050] In resin compositions comprising epoxy resin and a curing agent, when the curing agent comprises anhydride-based, amine-based, or phenol-based curing agents, the surface free energy of the cured product of such a resin composition generally tends to be relatively low. Therefore, typical photosensitive resin compositions tend to have poor wettability towards the cured product. When such a photosensitive resin composition with poor wettability towards the cured product forms a layer on a cured product layer, the surface of the photosensitive resin composition layer may become rough, or the thickness of the photosensitive resin composition layer may become uneven. In contrast, when the surface free energy of the cured product of a particular resin composition is within the aforementioned range, the photosensitive resin composition can have good wettability towards the cured product. Therefore, a uniform layer of the photosensitive resin composition can be formed on the surface of the cured product layer, thus sufficiently satisfying conditions (i) and (ii).
[0051] Furthermore, as mentioned above, when particles of the inorganic filler (C) detach from the surface of the cured layer, indentations can form on the traces left by the detached particles. Assuming the wettability of the photosensitive resin composition to the cured material is low, the aforementioned indentations can lead to increased surface roughness or thickness inhomogeneity of the photosensitive resin composition layer. Generally, the more inorganic filler (C) in a particular resin composition, the greater the frequency of particle detachment. Therefore, the specific surface free energy of the cured product of the particular resin composition is preferably set based on the amount of inorganic filler (C) particles. Specifically, the ratio of the inorganic filler (C) to 100% by mass of the non-volatile components of the particular resin composition is defined as R(C) [mass%], and the surface free energy of the cured product of the particular resin composition is defined as E [mJ / m³]. 2 In this case, the ratio R(C) / E is preferably 4.0 [mass%·m]. 2 Below [ / mJ], it is better to be 3.0 [mass%·m] 2 Below [ / mJ], especially preferably 2.5 [mass%·m] 2 Below [ / mJ]. A lower limit is preferably 0.1 [mass%·m]. 2 / mJ] or more, for example, could be 0.5 [mass%·m 2 / mJ] or above, 0.8 [mass%·m 2 / mJ] and above. When the ratio R(C) / E is within the range described above, the effect of the non-uniformity of the surface roughness and thickness of the layer of the photosensitive resin composition caused by the detachment of particles of inorganic filler material (C) can be suppressed. Therefore, a specific resin composition that fully satisfies conditions (i) and (ii) can usually be obtained, thereby achieving an effective improvement in resolution.
[0052] -toughness- As another method for obtaining a specific resin composition that fully satisfies conditions (i) and (ii), for example, a method of adjusting the composition of the specific resin composition to obtain a cured product having a specific range of toughness can be cited. Specifically, a method of adjusting the composition of the specific resin composition so that the cured product obtained by heat curing the specific resin composition at 150°C for 1 hour has a specific range of fracture toughness K1C. The fracture toughness K1C of the cured product is preferably in the range of 1.0 MPa·m. 1 / 2 The above is preferred, but 1.5 MPa·m is even better. 1 / 2 That's all. There's no specific upper limit; for example, it could be 10 MPa·m. 1 / 2 the following.
[0053] The fracture toughness K1C of the cured resin composition can be determined by the method described in the examples below.
[0054] As described below, when particles of the inorganic filler material detach from the surface of the cured layer of the resin composition containing the inorganic filler material, the surface of the photosensitive resin composition layer formed on the surface of the cured layer may become rough, or the thickness of the photosensitive resin composition layer may become uneven. In contrast, when the fracture toughness K1C of the cured resin composition is within the aforementioned range, the resin can firmly retain the particles of (C) the inorganic filler material. Specifically, when the fracture toughness K1C is within the aforementioned range, the resin can strongly resist the stress during abrasion, thus effectively suppressing the detachment of the particles of (C) the inorganic filler material. Therefore, conditions (i) and (ii) can be sufficiently satisfied. This is particularly effective when used for forming a layer of photosensitive resin composition on the abrasive surface of a cured material.
[0055] [2. Composition of the resin composition] One embodiment of the present invention relates to a specific resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents, and (C) an inorganic filler. The specific composition of the specific resin composition is set in a manner that satisfies the above conditions (i) and (ii), within the range of including components (A) to (C).
[0056] For example, when using epoxy resin (A) with a rigid structure containing aromatic rings, the elastic modulus of the cured product can generally be increased, or the toughness can be decreased. Conversely, when using epoxy resin (A) with a flexible structure containing aliphatic hydrocarbon chains, polybutadiene structures, polyoxyalkylene structures, etc., the elastic modulus of the cured product can generally be decreased, or the toughness can be increased. Furthermore, for example, the surface free energy of the cured product can be adjusted by the type of groups possessed by epoxy resin (A), thus, by selecting epoxy resin (A) with a suitable molecular structure, the surface free energy of the cured product can be adjusted. Furthermore, for example, by combining it with components (A) to (C) and further using suitable components, the elastic modulus, surface free energy, and toughness of the cured product can also be adjusted. By appropriately combining these methods, a specific resin composition that satisfies conditions (i) and (ii) above can be obtained. Hereinafter, examples of the composition of a specific resin composition will be described, but the composition of a specific resin composition is not limited to the composition described below.
[0057] [2.1.(A) Epoxy Resin] The specific resin composition involved in this embodiment includes (A) an epoxy resin. (A) An epoxy resin refers to a resin having epoxy groups.
[0058] Examples of epoxy resins (A) include, for instance, bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, triphenol type epoxy resins, phenol novolac type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins with a butadiene structure, alicyclic epoxy resins, alicyclic epoxy resins with an ester skeleton, heterocyclic epoxy resins, spirocyclic epoxy resins, cyclohexane type epoxy resins, cyclohexanediol type epoxy resins, tris(hydroxymethyl) type epoxy resins, tetraphenylethane type epoxy resins, and naphthylene ethers. Epoxy resins with fused ring skeletons, such as ether-type epoxy resins, tert-butylcatechol-type epoxy resins, naphthalene-type epoxy resins, naphthol-type epoxy resins, anthracene-type epoxy resins, and naphthol novolac-type epoxy resins; isocyanurate-type epoxy resins; epoxy resins containing alkylene oxy skeletons and butadiene skeletons; epoxy resins containing fluorene structures; etc. (A) Epoxy resins can be used alone or in combination of two or more.
[0059] From the viewpoint of obtaining a cured product of a specific resin composition with high elastic modulus and toughness, (A) epoxy resin may include epoxy resin containing an aromatic structure. An aromatic structure is generally defined as a chemical structure of aromaticity, and also includes polycyclic aromatics and aromatic heterocycles. Examples of epoxy resins containing an aromatic structure include, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, triphenol type epoxy resin, naphthol phenolic varnish type epoxy resin, phenol phenolic varnish type epoxy resin, tert-butylcatechol type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, bixylenol type epoxy resin, glycidylamine type epoxy resin with an aromatic structure, and glycidylamine type epoxy resin with an aromatic structure. Glyceryl ester type epoxy resin, cresol phenolic varnish type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin with aromatic structure, butadiene type epoxy resin with aromatic structure, alicyclic epoxy resin with aromatic structure, heterocyclic epoxy resin, spirocyclic epoxy resin with aromatic structure, cyclohexanediethanol type epoxy resin with aromatic structure, naphthyl ether type epoxy resin, trihydroxymethyl type epoxy resin with aromatic structure, tetraphenylethane type epoxy resin with aromatic structure, etc.
[0060] From the viewpoint of obtaining a cured product of a specific resin composition with excellent heat resistance, epoxy resins containing fused ring structures are preferred among epoxy resins containing aromatic structures. Examples of fused rings in epoxy resins containing fused ring structures include naphthalene rings, anthracene rings, and phenanthrene rings, with naphthalene rings being particularly preferred. Therefore, epoxy resin (A) preferably contains a naphthalene-type epoxy resin that contains a naphthalene ring structure. Generally, using a naphthalene-type epoxy resin can improve the elastic modulus and toughness of the cured product of the specific resin composition. Relative to 100% by mass of epoxy resin (A), the amount of naphthalene-type epoxy resin is preferably 10% by mass or more, more preferably 15% by mass or more, particularly preferably 20% by mass or more, preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0061] From the viewpoint of improving the heat resistance and metal adhesion of cured products of a particular resin composition, (A) epoxy resin may include glycidylamine type epoxy resin.
[0062] From the viewpoint of reducing the elastic modulus of the cured product of a particular resin composition, (A) the epoxy resin may include an epoxy resin having a butadiene structure.
[0063] The specific resin composition preferably comprises an epoxy resin having two or more epoxy groups in one molecule as epoxy resin (A). The proportion of epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, relative to 100% by mass of the non-volatile components of epoxy resin (A).
[0064] Epoxy resins include epoxy resins that are liquid at 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at 20°C (hereinafter sometimes referred to as "solid epoxy resins"). In the specific resin composition of this embodiment, the epoxy resin may consist only of liquid epoxy resin, or it may consist only of solid epoxy resin, or it may consist of a combination of liquid epoxy resin and solid epoxy resin, preferably consisting only of liquid epoxy resin.
[0065] As a liquid epoxy resin, it is preferable to be a liquid epoxy resin having two or more epoxy groups in one molecule.
[0066] As liquid epoxy resins, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidylamine type epoxy resin, phenolic varnish type epoxy resin, alicyclic epoxy resin with an ester skeleton, cyclohexane type epoxy resin, cyclohexanediol type epoxy resin, epoxy resin with a butadiene structure, epoxy resin containing an oxidized olefin skeleton and a butadiene skeleton, epoxy resin containing a fluorene structure, and dicyclopentadiene type epoxy resin are particularly preferred.
[0067] Specific examples of liquid epoxy resins include: DIC's "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resin); and Mitsubishi Chemical's "828US", "828EL", "jER828EL", "825", and "EPIKOTE". 828EL (Bisphenol A type epoxy resin); "jER807" and "1750" (Bisphenol F type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER152" (Phenolic varnish type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (Glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (Glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" (Glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" (Dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals Co., Ltd.; Nagase ChemteX's "EX-721" (glycidyl ester type epoxy resin); Nagase ChemteX's "EX-991L" (epoxy resin containing an oxide olefin backbone); Daicel's "Celloxide 2021P" (alicyclic epoxy resin with an ester backbone); Daicel's "PB-3600"; Nippon Soda's "JP-100" and "JP-200" (epoxy resins with butadiene structures); Nippon Steel & Sumitomo Metal Chemicals' "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin); Osaka Gas Chemical's "EG-280" (epoxy resin containing a fluorene structure); etc.
[0068] As a solid epoxy resin, it is preferable to be a solid epoxy resin having three or more epoxy groups in one molecule, and more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0069] As solid epoxy resins, the preferred types are xylenol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, cresol-phenolic varnish-type epoxy resins, dicyclopentadiene-type epoxy resins, triphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, and tetraphenylethane-type epoxy resins.
[0070] Specific examples of solid epoxy resins include DIC's "HP4032H" (naphthalene-type epoxy resin); DIC's "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resins); DIC's "N-690" (cresol phenolic varnish type epoxy resin); DIC's "N-695" (cresol phenolic varnish type epoxy resin); and DIC's "HP-7200," "HP-7200HH," and "HP-7200H" (dicyclopentadiene). Epoxy resins of various types; DIC's "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthyl ether type epoxy resin); Nippon Kayaku Co., Ltd.'s "EPPN-502H" (triphenol type epoxy resin); Nippon Kayaku Co., Ltd.'s "NC7000L" (naphthol phenolic varnish type epoxy resin); Nippon Kayaku Co., Ltd.'s "NC3000H", "NC3000", and "NC3000" (naphthol phenolic varnish type epoxy resin). 0L”, NC3100 (biphenyl type epoxy resin); Nippon Steel & Sumitomo Metal Chemicals Co., Ltd.'s “ESN475V” (naphthol type epoxy resin); Nippon Steel & Sumitomo Metal Chemicals Co., Ltd.'s “ESN485” (naphthol phenolic varnish type epoxy resin); Mitsubishi Chemical Co., Ltd.'s “YX4000H”, “YX4000”, “YL6121” (biphenyl type epoxy resin); Mitsubishi Chemical Co., Ltd.'s “YX4000HK” (bixylenol type epoxy resin); Mitsubishi Chemical Co., Ltd.'s “YX8800” (anthracite type epoxy resin). Resins); Mitsubishi Chemical's "YX7700" (phenolic varnish epoxy resin containing xylene structure); Osaka Gas Chemical's "PG-100" and "CG-500"; Mitsubishi Chemical's "YL7760" (bisphenol AF type epoxy resin); Mitsubishi Chemical's "YL7800" (fluorene type epoxy resin); Mitsubishi Chemical's "jER1010" (solid bisphenol A type epoxy resin); Mitsubishi Chemical's "jER1031S" (tetraphenylethane type epoxy resin), etc.
[0071] The amount of liquid epoxy resin is not particularly limited relative to the total amount of epoxy resin (A) 100% by mass, but preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass.
[0072] (A) The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Epoxy equivalent is the mass of resin containing one equivalent of epoxy groups. This epoxy equivalent can be determined according to JIS K7236.
[0073] (A) The weight-average molecular weight (Mw) of the epoxy resin is preferably 100–5000, more preferably 200–3000, and even more preferably 400–1500. The weight-average molecular weight of the resin can be determined by gel permeation chromatography (GPC) as a value converted from polystyrene.
[0074] The amount of epoxy resin (A) relative to 100% by mass of the non-volatile components in a particular resin composition is not particularly limited, but preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 3% by mass or more, preferably 20% by mass or less, more preferably 18% by mass or less, and particularly preferably 15% by mass or less.
[0075] The amount of (A) epoxy resin relative to 100% by mass of the resin component in a particular resin composition is not particularly limited, but is preferably 10% by mass or more, more preferably 20% by mass or more, particularly preferably 30% by mass or more, preferably 80% by mass or less, more preferably 70% by mass or less, and particularly preferably 50% by mass or less. Unless otherwise specified, the resin component in a particular resin composition refers to the non-volatile components in the particular resin composition other than (C) inorganic fillers.
[0076] [2.2.(B) Curing agent] The specific resin composition involved in this embodiment includes a curing agent (B). The curing agent (B) typically has the function of reacting with the epoxy resin (A) to cure the specific resin composition. In this embodiment, at least one selected from anhydride-based curing agents, amine-based curing agents, and phenolic curing agents is used as the curing agent (B). Using anhydride-based, amine-based, or phenolic curing agents generally suppresses warping of the cured product. Furthermore, conventionally, layers of photosensitive resin compositions formed on cured layers of specific resin compositions containing anhydride-based, amine-based, and phenolic curing agents tend to have poor resolution. In contrast, by using the specific resin composition involved in this embodiment, curing agent (B) selected from anhydride-based, amine-based, and phenolic curing agents can be used, simultaneously achieving improved resolution. One type of curing agent can be used alone, or two or more can be used in combination.
[0077] Anhydride-based curing agents include, for example, curing agents having one or more anhydride groups per molecule, preferably curing agents having two or more anhydride groups per molecule. Specific examples of anhydride-based curing agents include: phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and trimellitic acid. Polymer anhydrides include pyromellitic anhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenyl sulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(triphenylene trioxide), and styrene-maleic acid resin copolymerized with styrene and maleic acid. Commercially available anhydride-based curing agents include, for example, “HNA-100”, “MH-700”, “MTA-15”, “DDSA”, and “OSA” manufactured by New Japan Rika Co., Ltd.; “YH-306” and “YH-307” manufactured by Mitsubishi Chemical Co., Ltd.; and “HN-2200” and “HN-5500” manufactured by Hitachi Chemical Co., Ltd.
[0078] As amine-based curing agents, examples include curing agents having one or more, preferably two or more, amino groups within one molecule. Specific examples include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines, with aromatic amines being preferred. Amine-based curing agents are preferably primary or secondary amines, and more preferably primary amines. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), diphenyl diamino sulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-phenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino- 4-Hydroxyphenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Amine-based curing agents can be commercially available, such as SEIKA's "SEIKACURE-S", Nippon Kayaku Co.'s "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS", Mitsubishi Chemical's "EpicureW", and Sumitomo Seika's "DTDA".
[0079] Examples of phenolic curing agents include those having one or more, preferably two or more, hydroxyl groups bonded to aromatic rings such as benzene rings or naphthalene rings in one molecule. Among these, compounds having hydroxyl groups bonded to benzene rings are preferred. Furthermore, from the viewpoint of heat resistance and water resistance, phenolic curing agents with a novolac structure are preferred. Further, from the viewpoint of adhesion, nitrogen-containing phenolic curing agents are preferred, and phenolic curing agents containing a triazine skeleton are even more preferred. In particular, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, linear phenolic novolac curing agents containing a triazine skeleton are preferred.
[0080] Specific examples of phenolic curing agents include: MEH-7700, MEH-7810, MEH-7851, and MEH-8000H manufactured by Meiwa Chemical Co., Ltd.; NHN, CBN, and GPH manufactured by Nippon Kayaku Co., Ltd.; TD-2090, TD-2090-60M, LA-7052, LA-7054, LA-1356, LA-3018, LA-3018-50P, EXB-9500, HPC-9500, KA-1160, KA-1163, and KA-1165 manufactured by DIC Corporation; GDP-6115L, GDP-6115H, and ELPC75 manufactured by Kunei Chemical Co., Ltd.; and 2,2-diallylbisphenol A manufactured by Sigma-Aldrich.
[0081] (B) The equivalent amount of active groups in the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., even more preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The equivalent amount of active groups indicates the mass of curing agent per equivalent of active groups.
[0082] When the number of epoxy groups in (A) epoxy resin is set to 1, the number of active groups in (B) curing agent is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less. Here, "the number of epoxy groups in (A) epoxy resin" refers to the sum of all values obtained by dividing the mass of the non-volatile component of (A) epoxy resin present in the resin composition by the epoxy equivalent. Furthermore, "the number of active groups in (B) curing agent" refers to the sum of all values obtained by dividing the mass of the non-volatile component of (B) curing agent present in the resin composition by the active group equivalent.
[0083] (B) The amount of curing agent is not particularly limited relative to 100% by mass of the non-volatile component in a particular resin composition, but preferably 0.1% by mass or more, more preferably 1.0% by mass or more, particularly preferably 2.0% by mass or more, preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0084] The amount of (B) curing agent is not particularly limited relative to 100% by mass of the resin component in a particular resin composition, but preferably 1.0% by mass or more, more preferably 5.0% by mass or more, particularly preferably 10% by mass or more, preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less.
[0085] [2.3.(C) Inorganic filler materials] The specific resin composition involved in this embodiment includes (C) an inorganic filler. Cured products of the specific resin composition containing (C) an inorganic filler generally have a reduced coefficient of thermal expansion and suppress warping. Furthermore, conventionally, layers of photosensitive resin compositions formed on cured layers of specific resin compositions containing inorganic fillers tend to have poor resolution. In contrast, by using the specific resin composition involved in this embodiment, (C) an inorganic filler can be used, thus simultaneously achieving improved resolution.
[0086] Inorganic compounds are used as inorganic filler materials. Examples of inorganic filler materials include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Furthermore, spherical silica is preferred as silica. (C) One inorganic filler material may be used alone, or two or more may be used in combination.
[0087] The cumulative particle size D50 of the inorganic filler material (C) is preferably 0.2 μm or more, more preferably 0.3 μm or more, particularly preferably 0.4 μm or more, preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less. When using the inorganic filler material (C) with such a small cumulative particle size D50, depressions caused by the detachment of particles from the inorganic filler material (C) can be reduced. Therefore, it is possible to effectively suppress surface roughening of the photosensitive resin composition layer formed on the surface of the cured layer of the specific resin composition, or to prevent uneven thickness of the photosensitive resin composition layer.
[0088] (C) The cumulative particle size D90 of 90% of the inorganic filler material is preferably 2 μm or more, more preferably 3 μm or more, particularly preferably 3.5 μm or more, preferably 30 μm or less, more preferably 27 μm or less, further preferably 26 μm or less, and particularly preferably 25 μm or less. Such a small cumulative particle size D90 indicates that the (C) inorganic filler material does not contain large particles. Therefore, depressions caused by the detachment of particles from the (C) inorganic filler material can be reduced. Thus, it is possible to effectively suppress surface roughening of the photosensitive resin composition layer formed on the surface of the cured layer of the specific resin composition, or to suppress uneven thickness of the photosensitive resin composition layer.
[0089] From the viewpoint of improving the resolution of the photosensitive resin composition layer formed on the surface of the cured layer of a specific resin composition, it is preferable to have a uniform surface shape of the cured layer. Here, when particles of the (C) inorganic filler material are detached, from the viewpoint of making the size of the depressions formed in the detachment marks uniform and the surface shape of the cured layer uniform, it is preferable that the particle size of the (C) inorganic filler material is uniform. On the other hand, from the viewpoint of increasing the amount of (C) inorganic filler material contained in the specific resin composition and reducing the coefficient of thermal expansion, it is preferable that the particle size of the (C) inorganic filler material has a certain degree of distribution to increase the filling density of the (C) inorganic filler material particles. Considering these viewpoints, the parameters "D50 / D90" and "D90-D50" representing the particle size distribution of the (C) inorganic filler material can have suitable ranges.
[0090] Specifically, (C) the ratio D50 / D90 of the inorganic filler material, representing 50% of the cumulative particle size D50 to 90% of the cumulative particle size D90, is preferably 0.2 or more, more preferably 0.3 or more, particularly preferably 0.35 or more, preferably 0.8 or less, more preferably 0.7 or less, and even more preferably 0.65 or less. When the ratio D50 / D90 is within the aforementioned range, both the coefficient of linear thermal expansion of the cured resin composition and the resolution of the photosensitive resin composition layer formed on the cured layer are desirable.
[0091] Furthermore, (C) the difference between the 50% cumulative particle size D50 and the 90% cumulative particle size D90 of the inorganic filler material, D90-D50, is preferably 2 μm or more, more preferably 2.5 μm or more, particularly preferably 3 μm or more, preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 16 μm or less. When the difference D90-D50 is within the aforementioned range, both the coefficient of linear thermal expansion of the cured product of the particular resin composition and the resolution of the photosensitive resin composition layer formed on the cured product layer are good.
[0092] The 50% cumulative particle size D50 and 90% cumulative particle size D90 of the (C) inorganic filler material can be determined by laser diffraction-scattering based on the Mie scattering theory. Specifically, the particle size distribution of the (C) inorganic filler material can be prepared on a volume basis using a laser diffraction-scattering particle size distribution measuring device. Furthermore, the particle size with a cumulative frequency of 50% from its smallest particle size side (i.e., the median particle size) can be set as the 50% cumulative particle size D50. Additionally, the particle size with a cumulative frequency of 90% from its smallest particle size side can be set as the 90% cumulative particle size D90. The sample for measurement can be prepared by weighing 100 mg of (C) inorganic filler material and 10 g of methyl ethyl ketone into a vial and dispersing it ultrasonically for 10 minutes. For the sample being measured, a laser diffraction particle size distribution measuring device is used, employing blue and red light source wavelengths, to measure the volumetric particle size distribution of the inorganic filler material (C) in a flow cell manner. Based on the obtained particle size distribution, the 50% cumulative particle size D50 and the 90% cumulative particle size D90 can be calculated. Examples of laser diffraction particle size distribution measuring devices include the "LA-960" manufactured by Horiba Manufacturing Co., Ltd.
[0093] (C) The specific surface area of inorganic filler materials is preferably 1m². 2 / g or higher, preferably 1.5m 2 / g or higher, even better is 2m 2 / g or higher, especially 3m 2 / g or more. There is no particular upper limit, but 60m is preferred. 2 / g or less, 50m 2 / g or less or 40m 2 / g or less. The specific surface area can be obtained by using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) to adsorb nitrogen gas onto the sample surface and then calculating the specific surface area using the BET multi-point method.
[0094] Commercially available inorganic filler materials (C) include, for example, Nippon Steel & Sumitomo Metal Materials' "SP60-05", "SP507-05", and "ST7010-2"; Yatuma's "YC100C", "YA050C", "YA050C-MJE", and "YA010C"; DENKA's "UFP-30"; Tokuyama's "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N"; Yatuma's "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", "SO-C5", "SO-C6", "FE9 series", "FEB series", and "FED series"; and DENKA's "DAW-03", "DAW-10", "FB-105FD", and "UFP-30". However, these commercially available products typically do not possess the aforementioned particle size distribution. Therefore, for commercially available products, it is preferable to use them by crushing, mixing, grading, or a combination thereof in a manner that has the above-mentioned particle size distribution, and then adjusting them to a suitable particle size distribution.
[0095] From the perspective of improving moisture resistance and dispersibility, (C) inorganic filler materials are preferably treated with surface treatment agents. Examples of surface treatment agents include fluorinated silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, and titanate coupling agents. Furthermore, a single surface treatment agent can be used, or two or more can be used in any combination.
[0096] Commercially available surface treatment agents include, for example, "KBM403" (3-epoxypropoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd., "KBM-4803" (long-chain epoxy silane coupling agent) manufactured by Shin-Etsu Chemical Industry Co., Ltd., and "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Industry Co., Ltd.
[0097] From the perspective of improving the dispersibility of inorganic fillers, the degree of surface treatment by surface treatment agent is preferably within a specified range. Specifically, it is preferable that 100 parts by mass of inorganic filler have been surface treated with 0.2 to 5 parts by mass of surface treatment agent, more preferably with 0.2 to 3 parts by mass of surface treatment agent, and even more preferably with 0.3 to 2 parts by mass of surface treatment agent.
[0098] The degree of surface treatment by surface treatment agents can be evaluated by the carbon content per unit surface area of the inorganic filler. From the perspective of improving the dispersibility of inorganic fillers, the preferred carbon content per unit surface area of the inorganic filler is 0.02 mg / m². 2 The above is preferred, ideally 0.1 mg / m². 2 The above, and even better, is 0.2 mg / m². 2 That's all. On the other hand, from the viewpoint of suppressing the increase in melt viscosity of a specific resin composition and melt viscosity in sheet form, 1 mg / m³ is preferable. 2 The following is preferable: 0.8 mg / m² 2 The following is even better: 0.5 mg / m² 2 the following.
[0099] The carbon content per unit surface area of inorganic filler materials can be determined after cleaning the surface-treated inorganic filler material with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, sufficient MEK as a solvent is added to the surface-treated inorganic filler material, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the carbon content per unit surface area of the inorganic filler material is determined using a carbon analyzer. A carbon analyzer such as the "EMIA-320V" manufactured by Horiba Corporation can be used.
[0100] The amount of (C) inorganic filler material relative to 100% by mass of the non-volatile component in the specific resin composition is not particularly limited, but preferably 60% by mass or more, more preferably 65% by mass or more, further preferably 70% by mass or more, particularly preferably 75% by mass or more, preferably 95% by mass or less, more preferably 93% by mass or less, further preferably 92% by mass or less, and particularly preferably 90% by mass or less. The cured product of the specific resin composition containing such a range of amounts of (C) inorganic filler material can effectively reduce the coefficient of thermal expansion. Furthermore, conventional resin compositions containing such a large amount of inorganic filler material tend to have particularly poor resolution of the photosensitive resin composition layer formed on its cured layer. In contrast, the specific resin composition according to this embodiment contains such a large amount of (C) inorganic filler material while simultaneously improving resolution. Therefore, the specific resin composition according to this embodiment can simultaneously achieve a low coefficient of thermal expansion and excellent resolution, which were previously difficult to achieve simultaneously.
[0101] [2.4.(D) Silane Coupling Agents] In addition to components (A) to (C) described above, the specific resin composition described in this embodiment may further include (D) a silane coupling agent as an optional component. The silane coupling agent can improve the adhesion between the cured resin composition and the conductor layer. Furthermore, the silane coupling agent (D) can adjust the elastic modulus, surface free energy, and toughness of the cured resin composition.
[0102] Examples of silane coupling agents include aminosilane-based coupling agents, epoxysilane-based coupling agents, mercaptosilane-based coupling agents, alkoxysilane compounds, organosilazane compounds, and titanate-based coupling agents. Among these, epoxysilane-based coupling agents containing epoxy groups and mercaptosilane-based coupling agents containing mercapto groups are preferred, with epoxysilane-based coupling agents being particularly preferred. Furthermore, a single silane coupling agent can be used alone, or two or more can be used in combination.
[0103] Commercially available products can be used as silane coupling agents. Examples of commercially available silane coupling agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-epoxypropoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), and Shin-Etsu Chemical Co., Ltd.'s "SZ-3". 1" (hexamethyldisilazane), Shin-Etsu Chemical Industry Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Industry Co., Ltd.'s "KBM-4803" (long-chain epoxy silane coupling agent), Shin-Etsu Chemical Industry Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane), Shin-Etsu Chemical Industry Co., Ltd.'s "KBM503" (3-methacryloyloxypropyltrimethoxysilane), Shin-Etsu Chemical Industry Co., Ltd.'s "KBM5783", etc.
[0104] The amount of (D) silane coupling agent is not particularly limited relative to 100% by mass of the non-volatile component in a particular resin composition, but preferably 0.01% by mass or more, more preferably 0.05% by mass or more, particularly preferably 0.10% by mass or more, preferably 5.0% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.
[0105] The amount of (D) silane coupling agent is not particularly limited relative to 100% by mass of the resin component in a particular resin composition, but preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.5% by mass or more, preferably 10.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 3.0% by mass or less.
[0106] [2.5.(E) Curing Accelerator] In addition to the components (A) to (D) described above, the specific resin composition described in this embodiment may further include (E) a curing accelerator as an optional component. The curing accelerator (E) can effectively adjust the curing time of the specific resin composition.
[0107] Examples of (E) curing accelerators include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Among these, imidazole-based curing accelerators are preferred. A single curing accelerator can be used alone, or two or more can be used in combination.
[0108] Examples of phosphorus-based curing accelerators include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0109] Examples of amine-based curing accelerators include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, 1,8-diazabicyclo[5,4,0]undecene-7,4-dimethylaminopyridine, and 2,4,6-tris(dimethylaminomethyl)phenol, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0110] Examples of imidazole-based curing accelerators include 2-methylimidazolium, 2-undecylimidazolium, 2-heptadecylimidazolium, 1,2-dimethylimidazolium, 2-ethyl-4-methylimidazolium, 1,2-dimethylimidazolium, 2-ethyl-4-methylimidazolium, 2-phenylimidazolium, 2-phenyl-4-methylimidazolium, 1-benzyl-2-methylimidazolium, 1-benzyl-2-phenylimidazolium, 1-cyanoethyl-2-methylimidazolium, 1-cyanoethyl-2-undecylimidazolium, 1-cyanoethyl-2-ethyl-4-methylimidazolium, 1-cyanoethyl-2-phenylimidazolium, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine, 2,4- Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine isocyanuric acid adduct, 2-phenylimidazolyl isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazolium, 2-phenyl-4-methyl-5-hydroxymethylimidazolium, 2,3-dihydro-1H-pyrrole[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline and other imidazole compounds, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazolium and 1-benzyl-2-phenylimidazolium.
[0111] As an imidazole-based curing accelerator, commercially available products can be used, such as "P200-H50" manufactured by Mitsubishi Chemical Corporation, and "CUREZOL 2MZ", "2E4MZ", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", "Cl1Z-A", "2MZ-OK", "2MA-OK", "2MA-OK-PW", and "2PHZ" manufactured by Shikoku Chemical Industry Co., Ltd.
[0112] Examples of guanidine-based curing accelerators include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine, with dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene being preferred.
[0113] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) and cobalt(III) acetylacetone, organocopper complexes such as copper(II) acetylacetone, organozinc complexes such as zinc(II) acetylacetone, organoiron complexes such as iron(III) acetylacetone, organonickel complexes such as nickel(II) acetylacetone, and organomanganese complexes such as manganese(II) acetylacetone. Examples of organometallic salts include zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0114] The amount of (E) curing accelerator is not particularly limited relative to 100% by mass of the non-volatile component in a particular resin composition, but preferably 0.01% by mass or more, more preferably 0.10% by mass or more, particularly preferably 0.20% by mass or more, preferably 2.0% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.
[0115] The amount of (E) curing accelerator is not particularly limited relative to 100% by mass of the resin component in a particular resin composition, but preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 1.0% by mass or more, preferably 10.0% by mass or less, more preferably 6.0% by mass or less, and even more preferably 4.0% by mass or less.
[0116] [2.6.(F) Free radical polymerizable compounds] In addition to the components (A) to (E) described above, the specific resin composition described in this embodiment may further include (F) a free radical polymerizable compound as an optional component. The (F) free radical polymerizable compound can be used to adjust the electrical properties (dielectric constant, dielectric loss tangent, etc.) of the cured product of the specific resin composition. Furthermore, the (F) free radical polymerizable compound can typically be used to adjust the elastic modulus, surface free energy, and toughness of the cured product of the specific resin composition.
[0117] As (F) radical polymerizable compounds, compounds having olefinic unsaturated bonds can be used. Examples of such (F) radical polymerizable compounds include compounds having radical polymerizable groups such as vinyl, allyl, 1-butenyl, 2-butenyl, acryloyl, methacryloyl, fumaroyl, maleyl, vinylphenyl, styryl, cinnamoyl, and maleimide (2,5-dihydro-2,5-dioxo-1H-pyrrole-1-yl). One (F) radical polymerizable compound can be used alone, or two or more can be used in combination.
[0118] Specific examples of (F) radical polymerizable compounds include (meth)acrylic acid-based radical polymerizable compounds having one or more acryloyl groups and / or methacryloyl groups; styrene-based radical polymerizable compounds having one or more vinyl groups directly bonded to aromatic carbon atoms; allyl-based radical polymerizable compounds having one or more allyl groups; maleimide-based radical polymerizable compounds having one or more maleimide groups, etc. Among these, (meth)acrylic acid-based radical polymerizable compounds are preferred.
[0119] (F) radical polymerizable compounds preferably contain a polyalkylene oxide structure. By using (F) radical polymerizable compounds containing a polyalkylene oxide structure, the flexibility of the cured product of a particular resin composition can be improved, the warpage of the cured product can be reduced, or the adhesion between the cured product and the conductor layer can be improved. Furthermore, the elastic modulus of the cured product can usually be reduced, or the toughness can be improved.
[0120] The polyoxyethylene structure can be derived from formula (6): -(R f O) n - indicates. In equation (6), n usually represents an integer greater than 2. This integer n is preferably greater than 4, more preferably greater than 9, even more preferably greater than 11, usually less than 101, preferably less than 90, more preferably less than 68, and even more preferably less than 65. In equation (6), R fEach alkylene group may be independently represented as having substituents. The alkylene group preferably has 1 or more carbon atoms, more preferably 2 or more, more preferably 6 or less, more preferably 5 or less, further preferably 4 or less, further preferably 3 or less, and particularly preferably 2. Examples of substituents that may be present in the alkylene group include, for example, halogen atoms, -OH, alkoxy groups, primary or secondary amino groups, aryl groups, -NH2, -CN, -COOH, -C(O)H, -NO2, etc. Preferably, the alkyl group is unsubstituent. Specific examples of polyoxyethylene structures include polyethylene oxide structures, polypropylene oxide structures, polybutene oxide structures, poly(ethylene oxide-co-propylene oxide) structures, poly(ethylene oxide-ran-propylene oxide) structures, poly(ethylene oxide-alt-propylene oxide) structures, and poly(ethylene oxide-block-propylene oxide) structures.
[0121] (F) The number of polyoxyethylene structures contained in one molecule of a free radical polymerizable compound may be one or more. (F) The number of polyoxyethylene structures contained in one molecule of a free radical polymerizable compound is preferably two or more, more preferably four or more, further preferably nine or more, particularly preferably 11 or more, preferably 101 or less, more preferably 90 or less, further preferably 68 or less, and particularly preferably 65 or less. (F) When a free radical polymerizable compound contains two or more polyoxyethylene structures in one molecule, those polyoxyethylene structures may be the same or different from each other.
[0122] Examples of commercially available (F) radical polymerizable compounds containing polyoxyethylene structures include monofunctional acrylates “AM-90G”, “AM-130G”, and “AMP-20GY” manufactured by Shin-Nakamura Chemical Industry Co., Ltd.; difunctional acrylates “A-1000”, “A-B1206PE”, “A-BPE-20”, and “A-BPE-30”; monofunctional methacrylates “M-20G”, “M-40G”, “M-90G”, “M-130G”, and “M-230G”; and difunctional methacrylates “23G”, “BPE-900”, “BPE-1300N”, and “1206PE”. In addition, other examples include "LIGHT ESTER BC", "LIGHTESTER 041MA", "LIGHT ACRYLATE EC-A", and "LIGHT ACRYLATE EHDG-AT" manufactured by Kyoei Chemical Co., Ltd.; "FA-023M" manufactured by Hitachi Chemical Co., Ltd.; and "BLEMMER (registered trademark) PME-4000", "BLEMMER (registered trademark) 50POEO-800B", "BLEMMER (registered trademark) PLE-200", "BLEMMER (registered trademark) PLE-1300", "BLEMMER (registered trademark) PSE-1300", "BLEMMER (registered trademark) 43PAPE-600B", and "BLEMMER (registered trademark) ANP-300" manufactured by Nippon Oil Co., Ltd. Among them, the preferred ones are “M-130G” which has 13 polyoxyethylene structures (more specifically, polyoxyethylene structures) per molecule; and “M-230G” which has 23 polyoxyethylene structures (more specifically, polyoxyethylene structures) per molecule.
[0123] (F) The olefinic unsaturated bond equivalent of the free radical polymerizable compound is preferably 20 g / eq. to 3000 g / eq., more preferably 50 g / eq. to 2500 g / eq., even more preferably 70 g / eq. to 2000 g / eq., and particularly preferably 90 g / eq. to 1500 g / eq. The olefinic unsaturated bond equivalent indicates the mass of the free radical polymerizable compound per 1 olefinic unsaturated bond.
[0124] (F) The weight-average molecular weight (Mw) of the free radical polymerizable compound is preferably 150 or more, more preferably 250 or more, even more preferably 400 or more, preferably less than 40,000, more preferably less than 10,000, even more preferably less than 5,000, and particularly preferably less than 3,000.
[0125] The amount of (F) free radical polymerizable compound is not particularly limited relative to 100% by mass of the non-volatile component in a particular resin composition, but preferably 0.1% by mass or more, more preferably 1.0% by mass or more, particularly preferably 2.0% by mass or more, preferably 10.0% by mass or less, more preferably 6.0% by mass or less, and even more preferably 3.0% by mass or less.
[0126] The amount of (F) free radical polymerizable compound relative to 100% by mass of the resin component in a particular resin composition is not particularly limited, but preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.
[0127] [2.7. (G) Free radical polymerization initiators] In addition to the components (A) to (F) described above, the specific resin composition involved in this embodiment may further include a (G) free radical polymerization initiator as an optional component. Preferably, the (G) free radical polymerization initiator is a thermal polymerization initiator that generates free radicals upon heating. When the specific resin composition contains a (F) free radical polymerizable compound, the specific resin composition typically contains a (G) free radical polymerization initiator. One (G) free radical polymerization initiator may be used alone, or two or more may be used in combination.
[0128] Examples of (G) radical polymerization initiators include peroxide-based and azo-based free radical polymerization initiators. Among these, peroxide-based free radical polymerization initiators are preferred.
[0129] Examples of peroxide-based free radical polymerization initiators include hydrogen peroxide compounds such as 1,1,3,3-tetramethylbutylhydrogen peroxide; dialkyl peroxide compounds such as tert-butylisopropylbenzene peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne; and dilauroyl peroxide, didecanoyl peroxide, and dicarbonyl peroxide. Peroxide diacyl compounds such as cyclohexyl ester and bis(4-tert-butylcyclohexyl) peroxide dicarbonate; peroxide ester compounds such as tert-butyl peracetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, 1,1-dimethylpropyl 2-ethylperoxyhexanoate, tert-butyl 2-ethylperoxyhexanoate, tert-butyl 3,5,5-trimethylperoxyhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, and tert-butyl peroxymaleate; and so on.
[0130] Examples of azo nitrile compounds that serve as initiators for azo radical polymerization include 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), 2,2'-azobis(2,4-dimethylpentanonitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carboxynitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethylpentanonitrile; 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], and 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide]. Azoamide compounds such as [2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(2-methylpropionamide) dihydrate, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), etc.; alkylazo compounds such as 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane); etc.
[0131] (G) radical polymerization initiators preferably have intermediate-temperature activity. Specifically, (G) radical polymerization initiators preferably have a 10-hour half-life temperature T10 (°C) within a specific low temperature range. The 10-hour half-life temperature T10 is preferably 50°C to 110°C, more preferably 50°C to 100°C, and even more preferably 50°C to 80°C. Commercially available examples of such (G) radical polymerization initiators include, for example, "LUPEROX 531M80" manufactured by Arkema Fuji Co., Ltd., "PERHEXYL (registered trademark) O" manufactured by Nippon Yushi Co., Ltd., and "MAIB" manufactured by Fujifilm and Wako Pure Chemical Industries Co., Ltd.
[0132] The amount of (G) free radical polymerization initiator is not particularly limited relative to 100% by mass of the non-volatile component in a particular resin composition, but preferably 0.01% by mass or more, more preferably 0.02% by mass or more, particularly preferably 0.05% by mass or more, preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less.
[0133] [2.8. (H) Compounds containing a polyether backbone] In addition to the components (A) to (G) described above, the specific resin composition according to this embodiment may further include (H) a compound containing a polyether backbone as an optional component. The (H) compound containing a polyether backbone can suppress warping of the cured product of the specific resin composition. Furthermore, the (H) compound containing a polyether backbone can generally adjust the elastic modulus, surface free energy, and toughness of the cured product of the specific resin composition. One (H) compound containing a polyether backbone may be used alone, or two or more may be used in combination.
[0134] (H) Compounds containing a polyether backbone indicate polymer compounds having a polyether backbone. These (H) compounds containing a polyether backbone do not contain the components (A) to (G) described above. The polyether backbone contained in the (H) compound containing a polyether backbone is preferably a polyoxyalkylene backbone composed of one or more monomer units selected from ethylene oxide units and propylene oxide units. Therefore, the (H) compound containing a polyether backbone preferably does not contain a polyether backbone containing "monomer units with four or more carbon atoms such as butene oxide units and phenylene oxide units". Furthermore, the (H) compound containing a polyether backbone may contain hydroxyl groups.
[0135] (H) Compounds containing a polyether backbone may contain an organosilicon backbone. Examples of organosilicon backbones include: polydialkylsiloxane backbones such as polydimethylsiloxane backbones; polydiarylsiloxane backbones such as polydiphenylsiloxane backbones; polyalkylarylsiloxane backbones such as polymethylphenylsiloxane backbones; polydialkyl-diarylsiloxane backbones such as polydimethyl-diphenylsiloxane backbones; polydialkyl-alkylarylsiloxane backbones such as polydimethyl-methylphenylsiloxane backbones; polydiaryl-alkylarylsiloxane backbones such as polydiphenyl-methylphenylsiloxane backbones; etc., preferably polydialkylsiloxane backbones, and particularly preferably polydimethylsiloxane backbones. (H) Compounds containing a polyether backbone and containing an organosilicon backbone may be, for example, polyoxyalkylene-modified organosilicones, alkyletherified polyoxyalkylene-modified organosilicones (polyoxyalkylene-modified organosilicones in which at least a portion of the end of the polyether backbone is an alkoxy group), etc.
[0136] (H) Compounds containing a polyether backbone may contain a polyester backbone. This polyester backbone is preferably an aliphatic polyester backbone. The hydrocarbon chains contained in the aliphatic polyester backbone may be linear or branched, preferably branched. The number of carbon atoms contained in the polyester backbone may be, for example, 4 to 16. The polyester backbone may be derived from polybasic acids, lactones, or their anhydrous derivatives (anhydrides), therefore, (H) compounds containing a polyether backbone may have a carboxyl group at the end of the molecule, preferably a hydroxyl group at the end of the molecule.
[0137] Examples of compounds containing a polyether backbone (H) include linear polyoxyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol; polyoxyethylene glycerol ethers, polyoxypropylene glycerol ethers, polyoxyethylene trimethylolpropane ethers, polyoxypropylene trimethylolpropane ethers, polyoxyethylene diglycerol ethers, polyoxypropylene diglycerol ethers, polyoxyethylene pentaerythritol ethers, polyoxypropylene pentaerythritol ethers, polyoxyethylene sorbitol, polyoxypropylene sorbitol, polyoxyethylene polyoxypropylene sorbitol, etc. Polyoxyalkylene glycols (polyalkylene glycols) including chain-type polyoxyalkylene glycols (multi-chain polyalkylene glycols); polyoxyalkylene alkyl ethers including polyoxyethylene monoalkyl ethers, polyoxyethylene dialkyl ethers, polyoxypropylene monoalkyl ethers, polyoxypropylene dialkyl ethers, polyoxyethylene polyoxypropylene monoalkyl ethers, and polyoxyethylene polyoxypropylene dialkyl ethers; polyoxyalkylene esters (including acetates, propionates, butyrates, (meth)acrylates, etc.) including polyoxyethylene monoesters, polyoxyethylene diesters, polyoxypropylene monoesters, polyoxypropylene diesters, and polyoxyethylene polyoxypropylene monoesters; Polyoxyethylene polyoxypropylene diester, polyoxyethylene alkyl ether ester, polyoxypropylene alkyl ether ester, polyoxyethylene polyoxypropylene alkyl ether ester, etc., and polyoxyalkylene alkyl ether esters (including acetate, propionate, butyrate, (meth)acrylate, etc.); polyoxyethylene alkylamine, polyoxypropylene alkylamine, polyoxyethylene polyoxypropylene alkylamine, etc., and polyoxyalkylene alkylamine; polyoxyethylene alkylamide, polyoxypropylene alkylamide, polyoxyethylene polyoxypropylene alkylamide, etc., and polyoxyalkylene alkylamide; polyoxyethylene polydimethylsiloxane, polyoxypropylene polydimethylsiloxane, polyoxyethylene polyoxypropylene polydimethylsiloxane, polyoxyethylene polydimethylsiloxane, polyoxyethylene polydimethylsiloxane, polyoxypropylene polydimethylsiloxane, etc. Polyoxyalkylene-modified organosilicones such as silyloxyalkyl polydimethylsiloxane, polyoxyethylene polyoxypropylene polydimethylsiloxane, etc.; alkyl etherified polyoxyalkylene-modified organosilicones such as polyoxyethylene alkyl ether polydimethylsiloxane, polyoxypropylene alkyl ether polydimethylsiloxane, polyoxyethylene alkyl ether polydimethylsiloxane, polyoxyethylene alkyl ether polydimethylsiloxane, polyoxyethylene alkyl ether polydimethylsiloxane, polyoxypropylene alkyl ether polydimethylsiloxane, etc. (polyoxyalkylene-modified organosilicones with at least a portion of the polyether backbone terminal being alkoxy).
[0138] (H) The number-average molecular weight of the compound containing the polyether backbone is preferably 500–40,000, more preferably 500–20,000, and even more preferably 500–10,000. The weight-average molecular weight of the compound containing the polyether backbone is preferably 500–40,000, more preferably 500–20,000, and even more preferably 500–10,000. The number-average molecular weight and weight-average molecular weight can be determined by gel permeation chromatography (GPC) as values converted from polystyrene.
[0139] (H) The compound containing the polyether backbone is preferably liquid at 25°C. The viscosity of the compound containing the polyether backbone at 25°C is preferably below 100,000 mPa·s, more preferably below 50,000 mPa·s, further preferably below 30,000 mPa·s, further preferably below 10,000 mPa·s, further preferably below 5,000 mPa·s, further preferably below 4,000 mPa·s, further preferably below 3,000 mPa·s, further preferably below 2,000 mPa·s, and particularly preferably below 1,500 mPa·s. The lower limit of the viscosity of the compound containing the polyether backbone at 25°C is preferably above 10 mPa·s, more preferably above 20 mPa·s, further preferably above 30 mPa·s, further preferably above 40 mPa·s, and particularly preferably above 50 mPa·s. The viscosity can be the viscosity (mPa·s) measured using a type B viscometer.
[0140] Commercially available products containing (H) polyether backbones include, for example, "PLONON#102", "PLONON#104", "PLONON#201", "PLONON#202B", "PLONON#204", "PLONON#208", "Unilube70DP-600B", and "Unilube 70DP-950B" (polyoxyethylene polyoxypropylene glycol) manufactured by Nippon Oil Co., Ltd.; and "Pluronic L-23", "Pluronic L-31", "Pluronic L-44", "Pluronic L-61", "AdecaPluronic L-62", "Pluronic L-64", "Pluronic L-71", "Pluronic L-72", "Pluronic L-101", "Pluronic L-121", "Pluronic P-84", "Pluronic P-85", "Pluronic P-103", and "Pluronic P-84" manufactured by Adeka Co., Ltd. F-68, Pluronic F-88, Pluronic F-108, Pluronic 25R-1, Pluronic 25R-2, Pluronic 17R-2, Pluronic 17R-3, Pluronic 17R-4 (polyoxyethylene polyoxypropylene glycol); Shin-Etsu Silicones Co., Ltd.'s KF-6011, KF-6011P, KF-6012, KF-6013, KF-6015, KF-6016, KF-6017, KF-6017P, KF-6043, KF-6004, KF351A, KF352A, KF353, KF35 4L, KF355A, KF615A, KF945, KF-640, KF-642, KF-643, KF-644, KF-6020, KF-6204, X22-4515, KF-6028, KF-6028P, KF-6038, KF-6048, KF-6025 (polyoxyalkylene modified organosilicon), etc.
[0141] The amount of (H) polyether backbone compound relative to 100% by mass of the non-volatile component in a particular resin composition is not particularly limited, but preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.5% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0142] The amount of (H) compound containing a polyether backbone is not particularly limited relative to 100% by mass of the resin component in a particular resin composition, but preferably 0.1% by mass or more, more preferably 1.0% by mass or more, particularly preferably 5.0% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 12% by mass or less.
[0143] [2.9.(I) Other additives] In addition to the components (A) to (H) described above, the specific resin composition involved in this embodiment may further include any additives as any non-volatile components. Examples of such additives include organic fillers such as rubber particles, polyamide microparticles, and silicone particles; thermoplastic resins such as polycarbonate resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polysulfone resin, and polyester resin; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium dioxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; homogenizing agents such as silicone-based homogenizers and acrylic polymer-based homogenizers; thickeners such as Benton and montmorillonite; silicone-based defoamers; and acrylic polymer-based homogenizers. This product line includes defoamers such as fluoropolymer defoamers and vinyl resin defoamers; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; adhesion enhancers such as ureasilanes; adhesion enhancers such as triazole, tetraazole, and triazine adhesives; antioxidants such as hindered phenolic and hindered amine antioxidants; fluorescent whitening agents such as zirconia derivatives; surfactants such as fluorinated surfactants; flame retardants such as phosphorus-based (e.g., phosphate esters, phosphazene compounds, phosphonic acid compounds, red phosphorus), nitrogen-based (e.g., melamine sulfate), halogen-based, and inorganic (e.g., antimony trioxide). Additives can be used alone or in combination of two or more in any ratio.
[0144] [2.10.(J) Solvent] The specific resin composition involved in this embodiment may further contain any solvent as a volatile component. Examples of solvents include organic solvents. Furthermore, a single solvent may be used, or two or more may be used in combination in any ratio. The less solvent, the better. The amount of solvent relative to 100% by mass of the non-volatile component in the specific resin composition is preferably 3% by mass or less, more preferably 1% by mass or less, further preferably 0.5% by mass or less, further preferably 0.1% by mass or less, further preferably 0.01% by mass or less, and particularly preferably not contained in (0% by mass).
[0145] [3. Method for manufacturing the resin composition] The specific resin composition involved in this embodiment can be manufactured, for example, by mixing the above-described components. The components can be mixed partially or entirely simultaneously, or sequentially. During the mixing of the components, the temperature can be appropriately set, so heating and / or cooling can be performed temporarily or continuously. Furthermore, stirring or agitation can be performed during the mixing of the components.
[0146] [4. Properties of the Resin Composition] Typically, the aforementioned specific resin composition is thermosetting. Therefore, a cured product can be obtained by curing the specific resin composition with heat. When a layer of photosensitive resin composition is formed on the cured product layer formed by the specific resin composition, the resolution of the photosensitive resin composition layer can be good. Specifically, small openings can be formed on the photosensitive resin composition layer by exposure and development. Generally, the improved resolution can be achieved even when using any positive and negative photosensitive resin composition. For example, when the photosensitive resin composition layer is formed on the cured product layer of the specific resin composition by the method described in the [resolution evaluation test] of the examples described later, an opening with a diameter of 10 μm can be formed on the photosensitive resin composition layer.
[0147] The specific resin composition is preferably in paste form. Such a paste-like specific resin composition can be easily molded using compression molding. Therefore, it is easy to manufacture structures having a cured layer formed from a cured product of the specific resin composition and a layer of photosensitive resin composition formed in contact with the surface of the cured layer; and semiconductor chip packaging. The viscosity of the paste-like specific resin composition at 25°C can be in the range of 1 Pa·s to 1000 Pa·s, preferably in the range of 20 Pa·s to 500 Pa·s. The viscosity can be measured using an E-type viscometer.
[0148] From the viewpoint of sealing or insulating applications in semiconductor chip packaging, the cured product of a specific resin composition preferably has a small dielectric loss tangent. For example, the dielectric loss tangent of a cured product obtained by thermosetting a specific resin composition at 150°C for 60 minutes is preferably 0.03 or less, more preferably 0.025 or less, and even more preferably 0.02 or less. The lower limit can be 0.0001 or more. Furthermore, the cured product of a specific resin composition preferably has a small relative permittivity. For example, the relative permittivity of a cured product obtained by thermosetting a specific resin composition at 150°C for 60 minutes is preferably 3.7 or less, more preferably 3.6 or less, and even more preferably 3.5 or less. The lower limit can be 0.001 or more. The dielectric loss tangent and relative permittivity can be measured using the resonant cavity perturbation method with an HP8362B device manufactured by Agilent Technologies, at a measurement temperature of 23°C and a measurement frequency of 5.8 GHz.
[0149] [5. Uses of the resin composition] The specific resin composition described in this embodiment can preferably be used as a resin composition for sealing electronic devices such as organic EL devices and semiconductors (resin composition for sealing), particularly preferably as a resin composition for sealing semiconductors (resin composition for semiconductor sealing), and more preferably as a resin composition for sealing semiconductor chips (resin composition for semiconductor chip sealing). Furthermore, in addition to sealing applications, the resin composition can also be used as an insulating resin composition for insulating layers. For example, the resin composition can preferably be used as a resin composition for forming an insulating layer for semiconductor chip packages (resin composition for insulating layers of semiconductor chip packages), and as a resin composition for forming an insulating layer for circuit boards (including printed wiring boards) (resin composition for insulating layers of circuit boards).
[0150] From the viewpoint of fully utilizing the advantage of improving the resolution of the photosensitive resin composition layer formed on the cured layer of the specific resin composition, the specific resin composition involved in this embodiment is preferably used as a material for forming a sealing layer or insulating layer for semiconductor chip packages. Examples of semiconductor chip packages include FC-CSP, MIS-BGA package, ETS-BGA package, fan-out WLP (Wafer Level Package), fan-in WLP, fan-out PLP (Panel Level Package), and fan-in PLP.
[0151] In addition, the resin composition can also be used as an underfill material, for example, as a material for MUF (Molding Under Filling) used after a semiconductor chip is attached to a substrate.
[0152] Furthermore, the resin composition can be used in a wide range of applications employing the resin composition, such as resin sheets, prepregs and other sheet-like laminated materials, solder resists, chip soldering materials, via-filling resins, and component embedding resins.
[0153] [6. Resin Sheets] One embodiment of the present invention relates to a resin sheet having a support and a resin composition layer disposed on the support. The resin composition layer is a layer comprising a specific resin composition, typically formed from a specific resin composition.
[0154] From the perspective of thinness, the thickness of the resin composition layer is preferably less than 600 μm, more preferably less than 500 μm. The lower limit of the thickness of the resin composition layer is preferably more than 1 μm, more than 5 μm, more preferably more than 10 μm, even more preferably more than 50 μm, and particularly preferably more than 100 μm.
[0155] Furthermore, the thickness of the cured layer obtained by curing the resin composition layer is preferably 600 μm or less, more preferably 500 μm or less. The lower limit of the thickness of the cured layer is preferably 1 μm or more, 5 μm or more, more preferably 10 μm or more, further preferably 50 μm or more, and particularly preferably 100 μm or more.
[0156] Examples of supports include films made of plastic materials, metal foils, and release paper, with films and metal foils made of plastic materials being preferred.
[0157] When using a film formed of a plastic material as a support, examples of plastic materials include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"); acrylic polymers such as polycarbonate (hereinafter sometimes abbreviated as "PC"); polymethyl methacrylate (hereinafter sometimes abbreviated as "PMMA"); cyclic polyolefins; triacetyl cellulose (hereinafter sometimes abbreviated as "TAC"), polyether sulfide (hereinafter sometimes abbreviated as "PES"), polyether ketone, and polyimide. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0158] When using metal foil as a support, examples of metal foils include copper foil and aluminum foil. Among these, copper foil is preferred. As copper foil, foil formed from copper as a single metal can be used, or foil formed from an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used.
[0159] The surfaces of the support that are bonded to the resin composition layer can be treated with matte finish, corona treatment, antistatic treatment, etc.
[0160] Furthermore, as a support, a support with a release layer can be used on the surface that bonds to the resin composition layer. Examples of release agents for the release layer of a support with a release layer include, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins. Commercially available release agents include, for example, "SK-1," "AL-5," and "AL-7" manufactured by Lintec Corporation, which are alkyd resin-based release agents. Furthermore, examples of supports with a release layer include, for example, "Lumirror T60" manufactured by Toray Industries, Ltd.; "Purex" manufactured by Teijin Corporation; and "Unipeel" manufactured by UNITIKA Corporation.
[0161] The thickness of the support body is preferably in the range of 5μm to 75μm, and more preferably in the range of 10μm to 60μm. It should be noted that when using a support body with a release layer, it is preferable that the overall thickness of the support body with the release layer is within the above range.
[0162] Resin sheets can be manufactured, for example, by coating a specific resin composition onto a support using a die coater or similar coating apparatus. Alternatively, a specific resin composition can be dissolved in an organic solvent to prepare a resin varnish, which is then applied to manufacture resin sheets. By using an organic solvent, the viscosity can be adjusted, improving coatability. When using a specific resin composition or resin varnish containing an organic solvent, the specific resin composition or resin varnish is typically dried after coating to form a layer of the specific resin composition.
[0163] Examples of organic solvents include ketone solvents such as acetone, methyl ethyl ketone, and cyclohexanone; acetate solvents such as ethyl acetate, butyl acetate, acetic acid solvents, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitol solvents such as solvents and butyl carbitol; aromatic hydrocarbon solvents such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. Organic solvents can be used alone or in combination of two or more in any ratio.
[0164] Drying can be carried out by known methods such as heating or hot air blowing. Regarding drying conditions, drying is typically performed when the content of organic solvent in the resin composition layer is typically 10% by mass or less, preferably 5% by mass or less. Depending on the boiling point of the organic solvent in the specific resin composition or resin varnish, for example, when using a specific resin composition or resin varnish containing 30% to 60% by mass of organic solvent, the resin composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.
[0165] The resin sheet may include any layer other than the support and the resin composition layer, as needed. For example, in the resin sheet, a protective film, selected according to the support, may be provided on the side of the resin composition layer that is not bonded to the support (i.e., the side opposite to the support). The thickness of the protective film is, for example, 1 μm to 40 μm. The protective film prevents debris or other contaminants from adhering to the surface of the resin composition layer or causing damage. When the resin sheet has a protective film, the resin sheet can be used by peeling off the protective film. Furthermore, the resin sheet can be stored in rolls.
[0166] Resin sheets can be suitably used in the manufacture of semiconductor chip packages to form insulating layers (insulating resin sheets for semiconductor chip packages). For example, resin sheets can be used to form insulating layers for circuit boards (insulating resin sheets for circuit boards). Examples of packages using such substrates include FC-CSP, MIS-BGA packages, and ETS-BGA packages.
[0167] In addition, resin sheets can be suitable for sealing semiconductor chips (resin sheets for sealing semiconductor chips). Examples of suitable semiconductor chip packages include, for example, fan-out WLP, fan-in WLP, fan-out PLP, and fan-in PLP.
[0168] In addition, resin sheets can also be used as materials for MUFs used after semiconductor chips are attached to a substrate.
[0169] Furthermore, resin sheets can be used in a wide range of other applications requiring high insulation reliability. For example, resin sheets can be suitably used to form insulating layers for circuit boards such as printed wiring boards.
[0170] [7. Circuit board] One embodiment of the present invention relates to a circuit board comprising a cured product of a specific resin composition. Typically, the circuit board comprises a cured layer formed from a cured product of a specific resin composition, which functions as an insulating layer or a sealing layer. This circuit board can be manufactured, for example, by a manufacturing method including steps (1) and (2) described below. (1) A process of forming a resin composition layer on a substrate; (2) The process of heat curing the resin composition layer to form a cured layer.
[0171] In step (1), a substrate is prepared. Examples of substrates include glass epoxy boards, metal substrates (stainless steel, cold-rolled steel sheet (SPCC), etc.), polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. Additionally, as part of the substrate, a metal layer such as copper foil may be present on its surface. For example, a substrate with a peelable first metal layer and a second metal layer on both surfaces may also be used. When using such a substrate, a conductor layer that functions as a wiring layer for circuit wiring is typically formed on the side of the second metal layer opposite to the first metal layer. Examples of materials for the metal layer include copper foil, copper foil with a carrier, and materials for the conductor layer described later; copper foil is preferred. Examples of substrates with metal layers include the "Micro Thin" ultrathin copper foil with a carrier copper foil manufactured by Mitsui Mining & Metals Corporation.
[0172] Furthermore, a conductor layer may be formed on one or both surfaces of the substrate. In the following description, the component comprising the substrate and the conductor layer formed on the surface of the substrate is sometimes appropriately referred to as a "substrate with wiring layer". Examples of conductor materials included in the conductor layer include materials containing one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Single metals or alloys can be used as conductor materials. Examples of alloys include alloys of two or more metals selected from the group above (e.g., nickel-chromium alloys, copper-nickel alloys, and copper-titanium alloys). From the viewpoint of versatility, cost, and ease of pattern formation in conductor layer formation, alloys of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper as single metals; and alloys of nickel-chromium alloys, copper-nickel alloys, and copper-titanium alloys as alloys are preferred. Among these, single metals of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper; and nickel-chromium alloys are more preferred; and single metals of copper are particularly preferred.
[0173] For conductor layers, for example, to function as wiring layers, patterning can be performed. In this case, the linewidth (circuit width) / line spacing (width between circuits) ratio of the conductor layer is not particularly limited, but it is preferably 20 / 20 μm or less (i.e., a spacing of 40 μm or less), more preferably 10 / 10 μm or less, further preferably 5 / 5 μm or less, even more preferably 1 / 1 μm or less, and particularly preferably 0.5 / 0.5 μm or more. The spacing does not need to be uniform throughout the conductor layer. The minimum spacing of the conductor layer can be, for example, 40 μm or less, 36 μm or less, or 30 μm or less.
[0174] The thickness of the conductor layer varies depending on the design of the circuit board, preferably 3μm to 35μm, more preferably 5μm to 30μm, even more preferably 10μm to 20μm, and particularly preferably 15μm to 20μm.
[0175] After preparing the substrate, a resin composition layer is formed on the substrate. If a conductor layer is formed on the surface of the substrate, the resin composition layer is preferably formed by embedding the conductor layer within the resin composition layer.
[0176] The resin composition layer can be formed, for example, by compression molding. In compression molding, a substrate and a resin composition are typically placed in a mold, and pressure and heat are applied to the resin composition within the mold as needed to form a resin composition layer on the substrate.
[0177] The specific operation of compression molding can be performed as follows: An upper mold and a lower mold are prepared as molds for compression molding. A resin composition is then coated onto a substrate. The substrate coated with the resin composition is mounted onto the lower mold. Then, the upper and lower molds are closed, and heat and pressure are applied to the resin composition to perform compression molding.
[0178] Furthermore, the specific operation of compression molding can also be performed as follows: An upper mold and a lower mold are prepared as the molds for compression molding. The resin composition is carried on the lower mold. A substrate is then mounted on the upper mold. Then, the upper and lower molds are closed such that the resin composition carried on the lower mold is in contact with the substrate mounted on the upper mold, and heat and pressure are applied to perform compression molding.
[0179] Molding conditions vary depending on the composition of the specific resin composition, and suitable conditions can be adopted to achieve good sealing. For example, the mold temperature during molding is preferably above 70°C, more preferably above 80°C, particularly preferably above 90°C, preferably below 200°C, more preferably below 170°C, and particularly preferably below 150°C. Furthermore, the pressure applied during molding is preferably above 1 MPa, more preferably above 3 MPa, particularly preferably above 5 MPa, preferably below 50 MPa, more preferably below 30 MPa, and particularly preferably below 20 MPa. The curing time is preferably above 1 minute, more preferably above 2 minutes, particularly preferably above 3 minutes, preferably below 60 minutes, more preferably below 30 minutes, and particularly preferably below 20 minutes. Typically, the mold is removed after the resin composition layer has been formed. Mold removal can be performed before or after heat curing of the resin composition layer.
[0180] Furthermore, the resin composition layer can be formed, for example, by laminating a resin sheet with a substrate. This lamination can be performed, for example, by heating and pressing the resin sheet onto the substrate from the support side, thus bonding the resin composition layer with the substrate. Examples of components for heating and pressing the resin sheet onto the substrate (hereinafter sometimes referred to as "heat-pressing components") include, for example, heated metal plates (SUS end plates, etc.) or metal rollers (SUS rollers, etc.). It should be noted that, preferably, the heat-pressing component is not directly pressed onto the resin sheet, but rather pressed through an elastic material such as heat-resistant rubber, so that the resin sheet fully follows the surface irregularities of the substrate.
[0181] The lamination of the substrate and the resin sheet can be performed, for example, by vacuum lamination. In vacuum lamination, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C; the heating and pressing pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably in the range of 0.29 MPa to 1.47 MPa; and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination is preferably performed under reduced pressure conditions of 13 hPa or less.
[0182] After lamination, the heated pressing member is pressed under normal pressure (atmospheric pressure), for example, from the support side, thereby smoothing the laminated resin sheet. The pressing conditions for smoothing can be set to the same conditions as the heating and pressing conditions for lamination described above. It should be noted that lamination and smoothing can be performed continuously using a vacuum laminator.
[0183] After a resin composition layer is formed on a substrate, the resin composition layer is thermocured to form a cured layer. The thermocuring conditions of the resin composition layer may vary depending on the type of specific resin composition, but the curing temperature is usually in the range of 120°C to 240°C (preferably in the range of 150°C to 220°C, and more preferably in the range of 170°C to 200°C), and the curing time is usually in the range of 5 minutes to 120 minutes (preferably in the range of 10 minutes to 100 minutes, and more preferably in the range of 15 minutes to 90 minutes).
[0184] Before heat curing the resin composition layer, a preheating treatment can be performed on the resin composition layer at a temperature lower than the curing temperature. For example, before heat curing the resin composition layer, the resin composition layer can typically be preheated for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes) at a temperature of 50°C or higher and less than 120°C (preferably 60°C or higher and less than 110°C, more preferably 70°C or higher and less than 100°C).
[0185] As described above, a circuit board having a cured layer formed from a cured product of a specific resin composition can be manufactured. Furthermore, the method for manufacturing the circuit board may further include any steps. For example, when manufacturing a circuit board using a resin sheet, the method may include a step of peeling off a support from the resin sheet. The support may be peeled off before or after the thermal curing of the resin composition layer.
[0186] The manufacturing method of a circuit board may include, for example, a step of polishing the surface of a cured layer after it has been formed. There are no particular limitations on the polishing method. Examples of polishing methods include chemical mechanical polishing using a chemical mechanical polishing apparatus, mechanical polishing methods such as grinding, and surface grinding methods utilizing a rotating grinding stone.
[0187] The manufacturing method of a circuit board may include, for example, a process of interlayer bonding of conductor layers (3) and a process of drilling holes in a cured layer. This allows through-holes, vias, and other holes to be formed in the cured layer. Examples of methods for forming through-holes include laser irradiation, etching, and mechanical drilling. The size and shape of the through-holes can be appropriately determined according to the design of the circuit board. It should be noted that, for process (3), interlayer bonding can be performed by grinding or polishing the cured layer.
[0188] After forming the through-hole, it is preferable to perform a process to remove the smear material inside the through-hole. This process is sometimes referred to as the smear removal process. For example, when a conductor layer is formed on a cured layer by a plating process, a wet smear removal process can be performed on the through-hole. Alternatively, when a conductor layer is formed on a cured layer by a sputtering process, a dry smear removal process, such as a plasma treatment process, can be performed. Furthermore, the cured layer can also be roughened by the smear removal process.
[0189] Furthermore, the cured layer can be roughened before forming the conductive layer on it. This roughening process typically roughens the surface of the cured layer, including the interior of through-holes. Any roughening process, whether dry or wet, can be performed. Examples of dry roughening processes include plasma treatment. Examples of wet roughening processes include methods that sequentially perform swelling treatment using a swelling solution, roughening treatment using an oxidizing agent, and neutralization treatment using a neutralizing solution.
[0190] After forming through-holes, a conductor layer can be formed on the cured layer. By forming a conductor layer at the location where the through-holes are formed, the newly formed conductor layer becomes conductive with the conductor layer on the substrate surface, thus achieving interlayer bonding. Methods for forming the conductor layer include, for example, plating, sputtering, and vapor deposition. For instance, a suitable method such as semi-additive or fully additive plating can be used to plating the surface of the cured layer to form a conductor layer with the desired wiring pattern. Alternatively, when the support in the resin sheet is a metal foil, a subtractive method can be used to form a conductor layer with the desired wiring pattern. The material of the formed conductor layer can be a single metal or an alloy. Furthermore, the conductor layer can have a single-layer structure or a multilayer structure containing two or more layers of different types of materials.
[0191] Here, an example of an embodiment in which a conductor layer is formed on a cured layer is described in detail. A mask layer is formed on the surface of the cured layer, and an opening portion is formed in a part of the mask layer as a mask pattern. Then, after a metal layer is formed by sputtering, the mask layer is removed. Thus, a conductor layer having a desired wiring pattern can be formed. The mask layer is typically formed from a layer of photosensitive resin composition. Furthermore, the opening portion of the mask layer can be formed by exposing and developing the layer of photosensitive resin composition. A layer of photosensitive resin composition formed on a cured layer formed from a cured product of a specific resin composition can have excellent resolution. Therefore, a mask pattern can be formed as a small opening portion, and thus, fine wiring can be formed as a conductor layer.
[0192] The method for manufacturing a circuit board may include a step (4) of removing a substrate. By removing the substrate, a circuit board having a cured layer and a conductor layer embedded in the cured layer can be obtained. For example, this step (4) may be performed when a substrate having a peelable metal layer is used.
[0193] [8. Semiconductor Chip Packaging] One embodiment of the present invention relates to a semiconductor chip package comprising a cured product of a specific resin composition. Examples of such semiconductor chip packages include the following materials.
[0194] The first example involves a semiconductor chip package comprising the aforementioned circuit substrate and a semiconductor chip mounted on the circuit substrate. This semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit substrate.
[0195] Regarding the bonding conditions between the circuit board and the semiconductor chip, any condition that allows for conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board can be used. For example, the conditions used in flip-chip mounting of semiconductor chips can be employed. Alternatively, for example, bonding between the semiconductor chip and the circuit board can be achieved via an insulating adhesive.
[0196] As an example of bonding methods, one can cite the method of pressing a semiconductor chip onto a circuit board. As for the pressing conditions, the pressing temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the pressing time is usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).
[0197] In addition, as another example of bonding methods, a method of bonding semiconductor chips to a circuit board by reflow soldering can be cited. The reflow soldering conditions can be in the range of 120°C to 300°C.
[0198] After the semiconductor chip is bonded to the circuit board, it can be filled with a molding underfill material. The specific resin composition described above can be used as this molding underfill material.
[0199] The second example involves a semiconductor chip package comprising a semiconductor chip and a cured form of a specific resin composition that seals the semiconductor chip. In this type of semiconductor chip package, the cured form of the specific resin composition typically functions as a sealing layer. An example of the second example of a semiconductor chip package is a fan-out type WLP.
[0200] Figure 2 This is a schematic cross-sectional view illustrating a fan-out type WLP, which is an example of a semiconductor chip package according to this embodiment. The semiconductor chip package 100, as an example of a fan-out type WLP, is as follows: Figure 2 As shown, it includes: a semiconductor chip 110; a sealing layer 120 formed to cover the periphery of the semiconductor chip 110; a rewiring layer 130, which serves as an insulating layer, disposed on the side of the semiconductor chip 110 opposite to the sealing layer 120; a rewiring layer 140, which serves as a conductor layer; a solder mask layer 150; and bumps 160.
[0201] Such semiconductor chip packaging manufacturing methods include: (A) The process of laminating a temporary fixing film on a substrate; (B) The process of temporarily fixing a semiconductor chip onto a temporary fixing film; (C) The process of forming a sealing layer on a semiconductor chip; (D) The process of peeling the substrate and temporary fixing film from the semiconductor chip; (E) A process of forming a rewiring layer on the surface of a semiconductor chip after the substrate and temporary fixing film have been stripped. (F) The process of forming a redistribution layer as a conductor layer on the redistribution forming layer; and (G) The process of forming a solder resist layer on the redistribution layer. Furthermore, the above-described semiconductor chip package manufacturing method may include: (H) is the process of cutting multiple semiconductor chip packages into individual semiconductor chip packages to achieve monolithic packaging.
[0202] (Process (A)) Process (A) is the process of laminating a temporary fixing film on a substrate. The lamination conditions of the substrate and the temporary fixing film can be the same as the lamination conditions of the substrate and the resin sheet in the circuit board manufacturing method.
[0203] Examples of substrates include silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates such as FR-4 substrates obtained by infiltrating glass fibers with epoxy resin and then heat curing them; and substrates formed from bismaleimide triazine resins such as BT resin.
[0204] The temporary fixing film can be made of any material that can be peeled off from the semiconductor chip and temporarily fixed to the semiconductor chip. Examples of commercially available products include "REVALPHA" manufactured by Nitto Denko Corporation.
[0205] (Process (B)) Process (B) is the process of temporarily fixing the semiconductor chip onto a temporary fixing film. Temporary fixing of the semiconductor chip can be performed using devices such as flip chip bonders or die bonders. The layout and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixing film, the production quantity of the target semiconductor chip package, etc. For example, the semiconductor chips can be arranged in a matrix with multiple rows and columns for temporary fixing.
[0206] (Process (C)) Step (C) is the process of forming a sealing layer on a semiconductor chip. The sealing layer may be formed from a cured product of a specific resin composition. The sealing layer is typically formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of thermally curing the resin composition layer to form a cured layer serving as the sealing layer. The formation of the resin composition layer on the semiconductor chip may be performed, for example, by a method similar to the method for forming a resin composition layer on a substrate described above in [7. Circuit Board], except that a semiconductor chip is used instead of a substrate.
[0207] After forming a resin composition layer on a semiconductor chip, the resin composition layer is thermally cured to obtain a sealing layer covering the semiconductor chip. This seals the semiconductor chip using a cured product of a specific resin composition. The thermal curing conditions for the resin composition layer can be the same as those used in the method for manufacturing a circuit board. Furthermore, before thermally curing the resin composition layer, a preheating treatment can be performed on the resin composition layer at a temperature lower than the curing temperature. The preheating treatment conditions can be the same as those used in the preheating treatment method for manufacturing a circuit board.
[0208] (Process (D)) Process (D) is the process of peeling the substrate and temporary fixing film from the semiconductor chip. Ideally, the peeling method should be suitable for the material of the temporary fixing film. Examples of peeling methods include heating, foaming, or expanding the temporary fixing film. Another example is peeling by irradiating the temporary fixing film with ultraviolet light through the substrate, thereby reducing the adhesion of the temporary fixing film.
[0209] In methods of peeling off temporary fixation films by heating, foaming, or expanding them, the heating conditions are typically 100°C to 250°C for 1 to 90 seconds or 5 to 15 minutes. Alternatively, in methods of peeling off temporary fixation films by reducing their adhesiveness through ultraviolet (UV) irradiation, the UV irradiation dose is typically 10 mJ / cm². 2 ~1000mJ / cm 2 .
[0210] As described above, when the substrate and temporary fixing film are peeled off from the semiconductor chip, the surface of the sealing layer is exposed. The semiconductor chip package manufacturing method may include grinding the exposed surface of the sealing layer. Grinding improves the smoothness of the sealing layer surface. As a grinding method, the same method described in the circuit board manufacturing method can be used.
[0211] (Process (E)) Process (E) is the process of forming a rewiring layer as an insulating layer on the surface of the semiconductor chip after the substrate and temporary fixing film have been stripped. Typically, this rewiring layer is formed on the semiconductor chip and the sealing layer.
[0212] The material for the redistribution layer can be any insulating material. When a sealing layer is formed using a cured product of a specific resin composition, the redistribution layer formed on this sealing layer is preferably formed using a photosensitive resin composition. When the redistribution layer is formed on a cured layer of the specific resin composition as a layer of the photosensitive resin composition, the resolution of the redistribution layer can be excellent. Therefore, through-holes can be formed as small openings.
[0213] After forming the redistribution layer, vias are typically formed on the redistribution layer to enable interlayer bonding between the semiconductor chip and the redistribution layer. When the redistribution layer is formed using a photosensitive resin composition, the method for forming the vias typically involves exposing the surface of the redistribution layer through a mask. Examples of active energy rays include ultraviolet light, visible light, electron beams, and X-rays, with ultraviolet light being particularly preferred. Examples of exposure methods include, for example, contact exposure where the mask is in close contact with the redistribution layer, and non-contact exposure where the mask is not in close contact with the redistribution layer and parallel light is used for exposure.
[0214] Through the aforementioned exposure, a latent image can be formed in the rewire forming layer. Therefore, by subsequent development, a portion of the rewire forming layer is removed, creating a via as an opening penetrating the rewire forming layer. Regarding development, either wet development or dry development can be used. Examples of development methods include immersion, puddle, spray, brush, and scraping. From a resolution perspective, puddle is preferred.
[0215] The shape of the via is not particularly limited, but it is generally circular (approximately circular). The top diameter of the via is preferably 50 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, particularly preferably 10 μm or less, and even more preferably 5 μm or less. Here, the top diameter of the via refers to the opening diameter of the via on the surface of the redistribution layer.
[0216] (Process (F)) Process (F) is the process of forming a rewiring layer as a conductor layer on the rewiring forming layer. The method of forming the rewiring layer on the rewiring forming layer can be the same as the method of forming a conductor layer on a cured layer in the circuit board manufacturing process. In addition, processes (E) and (F) can be performed repeatedly, and the rewiring layer and the rewiring forming layer can be alternately stacked (build-up).
[0217] (Process (G)) Step (G) is the process of forming a solder mask layer on the redistribution layer. The solder mask layer can be made of any insulating material. From the viewpoint of ease of semiconductor chip packaging manufacturing, photosensitive resin compositions and thermosetting resin compositions are preferred. Furthermore, specific resin compositions can be used as thermosetting resin compositions.
[0218] Furthermore, in process (G), bump machining can be performed as needed to form bumps. Bump machining can be performed using methods such as solder balls or solder plating. Additionally, the formation of through-holes during bump machining can be performed in the same manner as in process (E).
[0219] (Process (H)) In addition to steps (A) to (G), the semiconductor chip packaging manufacturing method may also include step (H). Step (H) is the process of dicing multiple semiconductor chip packages into individual semiconductor chip packages for monolithic fabrication. There are no particular limitations on the method of dicing semiconductor chip packages into individual semiconductor chip packages.
[0220] As a third example involving semiconductor chip packaging, examples include: Figure 2 The example shown is a semiconductor chip package 100 in which a redistribution layer 130 or a solder resist layer 150 is formed from a cured product of a specific resin composition.
[0221] [9. Structure] As described above, in the methods for manufacturing circuit boards and semiconductor chip packages, as intermediate products, a structure comprising a "cured layer formed from a cured product of a specific resin composition that is a thermosetting resin composition" and a "layer of photosensitive resin composition formed on the surface of the cured layer" can be obtained. For example, in the method for manufacturing circuit boards, when a photosensitive resin composition is used to form a mask layer for forming a conductor layer, a structure comprising a substrate, a cured layer formed on the substrate from a cured product of a specific resin composition, and a mask layer formed on the cured layer from a photosensitive resin composition can be obtained. Furthermore, for example, in the method for manufacturing semiconductor chip packages, when a redistribution layer is formed from a photosensitive resin composition, a structure comprising a sealing layer formed from a cured product of a specific resin composition and a redistribution layer formed on the sealing layer from a photosensitive resin composition can be obtained.
[0222] In the structure described above, the photosensitive resin composition layer, such as the mask layer and the redistribution layer, can be disposed in a manner that is directly in contact with the cured layer formed from the cured product of the specific resin composition. Here, "directly" means that there are no other layers between the cured layer and the photosensitive resin composition layer.
[0223] When the photosensitive resin composition layers such as mask layers and redistribution layers are cured, the surface of the layer obtained by curing the photosensitive resin composition layers (hereinafter sometimes referred to as the "cured composition layer") opposite to the cured layer can generally have an arithmetic mean roughness Ra within the same range as specified in condition (i) above. Therefore, the photosensitive resin composition layer before curing can have a lower roughness corresponding to the arithmetic mean roughness Ra of the surface of the cured composition layer. Furthermore, the cured composition layer obtained by curing the photosensitive resin composition layers such as mask layers and redistribution layers can generally have a maximum thickness to minimum thickness difference TTV within the same range as specified in condition (ii) above. Therefore, the photosensitive resin composition layer before curing can have high thickness uniformity corresponding to the maximum thickness to minimum thickness difference TTV of the cured composition layer. Therefore, the photosensitive resin composition layer can obtain excellent resolution. Therefore, in the circuit board and semiconductor chip package according to the above embodiments, fine wiring can be formed. The curing conditions for the layer of the photosensitive resin composition can be adapted to the composition of the photosensitive resin composition, for example, at 250°C for 2 hours.
[0224] [10. Semiconductor Devices] Semiconductor devices are packaged with semiconductor chips. Examples of semiconductor devices include various semiconductor devices used in electrical products (such as computers, mobile phones, smartphones, tablets, wearable devices, digital cameras, medical devices, and televisions) and vehicles (such as motorcycles, automobiles, trams, ships, and aircraft). Example
[0225] Hereinafter, embodiments of the present invention will be shown to illustrate the invention in detail. However, the present invention is not limited to the embodiments described below. In the following description, unless otherwise specified, "parts" and "%" are based on mass. Furthermore, unless otherwise specified, the operations described below are performed at room temperature and pressure (23°C, 1 atm). In the following description, unless otherwise specified, the weight-average molecular weight Mw and number-average molecular weight Mn are obtained by gel permeation chromatography (GPC) using standard polystyrene.
[0226] [Manufacturing Example 1. Manufacturing of a photosensitive polyimide precursor (polymer A-1) as the first polymer] 155.1 g of 4,4'-oxophthalic dianhydride (ODPA) was placed in a 2-liter detachable flask, along with 134.0 g of 2-hydroxyethyl methacrylate (HEMA) and 400 ml of γ-butyrolactone. 79.1 g of pyridine was added while stirring at room temperature to obtain the reaction mixture. After the exothermic reaction was complete, the mixture was cooled to room temperature and allowed to stand for 16 hours.
[0227] Prepare a solution by dissolving 206.3 g of dicyclohexylcarbodiimide (DCC) in 180 ml of γ-butyrolactone. Add this solution to the reaction mixture over 40 minutes while stirring, under ice-cooling conditions. Next, 93.0 g of 4,4'-diaminodiphenyl ether (DADPE) is suspended in 350 ml of γ-butyrolactone to obtain a suspension. Add this suspension to the reaction mixture over 60 minutes while stirring. Further, after stirring the reaction mixture at room temperature for 2 hours, 30 ml of ethanol is added, and stirring continues for 1 hour. Then, 400 ml of γ-butyrolactone is added to the reaction mixture. Remove the precipitate formed in the reaction mixture by filtration to obtain the reaction solution.
[0228] The resulting reaction solution was added to 3 liters of ethanol, producing a precipitate of crude polymer. The crude polymer was filtered and dissolved in 1.5 liters of tetrahydrofuran to obtain a crude polymer solution. This crude polymer solution was added dropwise to 28 liters of water, causing the polymer to precipitate. The precipitate was filtered and then vacuum dried to obtain polymer A-1 as the first polymer. The weight-average molecular weight (Mw) of polymer A-1 was determined to be 20,000.
[0229] [Manufacturing Example 2. Manufacturing of a photosensitive polyimide precursor (polymer A-2) as a second polymer] Except that 147.1 g of 3,3',4'-biphenyltetracarboxylic dianhydride was used instead of 155.1 g of 4,4'-oxobisphthalic dianhydride, polymer A-2, as the second polymer, was manufactured using the same method as in Manufacturing Example 1. The weight-average molecular weight (Mw) of polymer A-2 was determined to be 22,000.
[0230] [Manufacturing Example 3. Manufacturing of a negative photosensitive resin composition as a first specific composition] Polymer A-150g, polymer A-250g, compound of formula (1) 2g, tetraethylene glycol dimethacrylate 8g, 2-nitroso-1-naphthol 0.05g, N-phenyldiethanolamine 4g, N-(3-(triethoxysilyl)propyl)o-carbamoylbenzoic acid 0.5g, and benzophenone-3,3'-bis(N-(3-triethoxysilyl)propionamide)-4,4'-dicarboxylic acid 0.5g were dissolved in a mixed solvent of N-methylpyrrolidone and ethyl lactate (weight ratio of N-methylpyrrolidone:ethyl lactate = 8:2) to obtain a negative photosensitive resin composition as a first specific composition. The amount of mixed solvent was adjusted so that the viscosity of the obtained negative photosensitive resin composition was 35 poise.
[0231] [Chemical Formula 5]
[0232] [Manufacturing Example 4. Manufacturing of polybenzoxazole precursor (polymer I) as a third polymer] In a 0.2-liter flask equipped with a stirrer and thermometer, 60 g of N-methylpyrrolidone was added, followed by 13.92 g (38 mmol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and the mixture was stirred to dissolve. Then, while maintaining the temperature at 0°C–5°C, 10.69 g (40 mmol) of dodecanoic acid dichloroisocyanurate was added dropwise over 10 minutes, and the solution in the flask was stirred for 60 minutes. The solution was then added to 3 liters of water, resulting in a precipitate. The precipitate was recovered, washed three times with pure water, and subjected to reduced pressure to obtain polyhydroxyamide (polybenzoxazole precursor) (hereinafter referred to as Polymer I). Polymer I has a weight-average molecular weight of 33,100 and a dispersion of 2.0.
[0233] [Manufacturing Example 5. Manufacturing of a positive photosensitive resin composition as a second specific composition] 100 parts of polymer I, 15 parts of acid-modified alkylated melamine-formaldehyde (hexamethoxymethylmelamine; "CYMEL 300" manufactured by Allnex), 11 parts of photosensitizer (1-naphthoquinone-2-diazido-5-sulfonate; "TPPA528" manufactured by Daito Chemix), and 200 parts of γ-butyrolactone were mixed to obtain a positive photosensitive resin composition as a second specific composition.
[0234] [Manufacturing Example 6. Manufacturing of Polyether Polyol A] In a reaction vessel, 22.6 g of ε-caprolactone monomer (PLACCEL M, manufactured by Daicel), 10 g of polypropylene glycol (polypropylene glycol, diol type, 3000 (manufactured by Fujifilm and Kohden Chemical Co., Ltd.), and 1.62 g of tin(II) 2-ethylhexanoate (manufactured by Fujifilm and Kohden Chemical Co., Ltd.) were added. The mixture was heated to 130°C under a nitrogen atmosphere and stirred for approximately 16 hours to allow the reaction to proceed. The product was dissolved in chloroform, precipitated again with methanol, and then dried to obtain polyether polyol resin A containing hydroxyl-terminated aliphatic backbone. According to GPC analysis, the number average molecular weight Mn of polyether polyol resin A was 9000.
[0235] [Manufacturing Example 7. Manufacturing of Negative Photosensitive Resin Composition N1 for Resolution Evaluation] A negative photosensitive resin composition N1 is prepared by mixing 10 parts by weight of cresol phenolic varnish resin ("TR4020G" manufactured by Asahi Organic Materials Co., Ltd.), 5 parts by weight of biphenyl aralkyl resin ("MEHC-7851SS" manufactured by Meiwa Chemical Co., Ltd.), 5 parts by weight of special bisphenol ("BisE" manufactured by Honshu Chemical Co., Ltd.), 5 parts by weight of compound containing at least two alkoxymethyl groups in the molecule ("MW-390" manufactured by Sanwa Chemical Co., Ltd.), 0.05 parts by weight of photoacid generator ("MP-triazine" manufactured by Sanwa Chemical Co., Ltd.), 6 parts by weight of organic filler material ("MM-101SM" manufactured by Negami Kogyo Co., Ltd.), and 30 parts by weight of propylene glycol monomethyl ether acetate (PGMEA, manufactured by Junsei Chemical Co., Ltd.).
[0236] [Manufacturing Example 8. Manufacturing of Positive Photosensitive Resin Composition P1 for Resolution Evaluation] (Synthesis of elastomer A:) 55 g of ethyl lactate was weighed into a 100 ml three-necked flask equipped with a stirrer, a nitrogen inlet tube, and a thermometer. Separately weighed polymerizable monomers (34.7 g of n-butyl acrylate, 2.2 g of dodecyl acrylate, 3.9 g of acrylic acid, 1.7 g of 1,2,2,6,6-pentamethylpiperidin-4-yl methacrylate, and 2.6 g of hydroxybutyl acrylate) and 0.29 g of azobisisobutyronitrile (AIBN) were added. While stirring at approximately 160 rpm at room temperature, nitrogen gas was introduced at a flow rate of 400 ml / min for 30 minutes to remove dissolved oxygen. Then, the nitrogen inlet was stopped, the flask was sealed, and the temperature was raised to 65 °C in a constant temperature water bath over approximately 25 minutes. The polymerization reaction was carried out at the same temperature for 10 hours to obtain acrylic elastomer A. The weight-average molecular weight of acrylic elastomer A is approximately 22,000.
[0237] (Preparation of positive photosensitive resin composition) The following mixture was prepared: 16.8 parts of a phenolic resin with a dicyclopentadiene ring (JFE Chemical Co., Ltd., "J-DPP-140"), 50.3 parts of a copolymer of 4-hydroxystyrene / styrene (70 / 30 molar ratio) (Maruzen Petrochemical Co., Ltd., "MARUKA LYNCUR CST"), 7.5 parts of an o-quinone diazide compound (Daito Chemix Co., Ltd., "PA-28"), 7.5 parts of an o-quinone diazide compound (Daito Chemix Co., Ltd., "4C-PA-280"), 10 parts of acid-modified alkylated melamine-formaldehyde (hexamethoxymethylmelamine; Allnex Co., Ltd., "CYMEL 300"), 7 parts of an epoxy compound (Nissan Chemical Industry Co., Ltd., "TEPIC-VL"), and elastomer A. A positive photosensitive resin composition P1 is prepared by combining 30 parts of 5-aminotetrazole ("HAT" manufactured by Toyoboki Co., Ltd.), 1 part of silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.), 3 parts of 4,4'-(1-(4-(1-(4-hydroxyphenyl)-1-methylethyl)-phenyl)-ethylidene)-bisphenol ("TrisP-PA-MF" manufactured by Honshu Chemical Co., Ltd.), 160 parts of ethyl lactate, and 5 parts of 1-methoxy-2-propanol.
[0238] [Examples 1-9 and Comparative Examples 1-2] The components shown in Table 1 below are mixed in the amounts (parts by mass) shown in Table 1 below to obtain a resin composition. For the articles shown in Table 1 below, the amount of solid components (non-volatile components) can be expressed as the amount of substance obtained from the solution. Furthermore, the details of each component shown in Table 1 are described below.
[0239] (A)Ingredients: Celloxide 2021P: Liquid alicyclic epoxy resin with an ester backbone (Celloxide 2021P manufactured by Daicel, epoxy equivalent 126 g / eq.); HP4032D: Liquid naphthalene-type epoxy resin ("HP4032D" manufactured by DIC Company, epoxy equivalent 151g / eq.); EX-991L: Liquid epoxy resin containing an olefinic skeleton (manufactured by Nagase ChemteX, “EX-991L”, epoxy equivalent 450 g / eq.); EG-280: Liquid epoxy resin containing fluorene structure (EG-280 manufactured by Osaka Gas Chemical Co., Ltd., epoxy equivalent 460 g / eq.); EP-3950L: Liquid glycidylamine type epoxy resin (ADEKA "EP-3950L", epoxy equivalent 95g / eq.); EP-3980S: Liquid glycidylamine type epoxy resin (ADEKA "EP-3980S", epoxy equivalent 115g / eq.); EP-4088S: Liquid dicyclopentadiene-type epoxy resin (ADEKA "EP-4088S", epoxy equivalent 170 g / eq.); ZX1059: A liquid 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin (manufactured by Nippon Steel Chemical Materials Co., Ltd., “ZX1059”, epoxy equivalent 169g / eq.); JP-100: An epoxy resin with a butadiene structure (JP-100 manufactured by Nippon Soda Co., Ltd., epoxy equivalent 210 g / eq.).
[0240] (B) Ingredients: 2,2-Dialylbisphenol A: Phenolic curing agent (manufactured by Sigma-Aldrich, active group equivalent 154 g / eq.); KAYAHARD AA: Amine-based curing agent (4,4'-diamino-3,3'-diethyldiphenylmethane, "KAYAHARDA-A" manufactured by Nippon Kayaku, active group equivalent (active hydrogen equivalent) 64 g / eq.); MH-700: Anhydride-based curing agent (MH-700 manufactured by Shin Nippon Rikan Co., Ltd., active group equivalent 164 g / eq.).
[0241] (C) Ingredients: Silica A: Silica particles (50% cumulative particle size D50 = 1.5 μm, 90% cumulative particle size D90 = 3.5 μm, specific surface area 2.78 m²) 2 / g). Substances that have undergone surface treatment with KBM573 (manufactured by Shin-Etsu Chemical Co., Ltd.); Silica B: Silica particles (50% cumulative particle size D50 = 4 μm, 90% cumulative particle size D90 = 12 μm, specific surface area 3.01 m²) 2 / g). Substances that have undergone surface treatment with KBM573 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0242] (D) Ingredients: KBM-803: 3-Mercaptopropyltrimethoxysilane (Shin-Etsu Chemical Industry Co., Ltd., "KBM803"); KBM-403: 3-Epoxypropoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., "KBM403").
[0243] (E) Components: 2E4MZ: Imidazole-based curing accelerator (2E4MZ manufactured by Shikoku Chemical Industry Co., Ltd.); 2MA-OK-PW: Imidazole-based curing accelerator (manufactured by Shikoku Chemical Co., Ltd. as "2MA-OK-PW").
[0244] (F)Ingredients: M-130G: A compound having a methacryloyl group and a polyethylene oxide structure (M-130G manufactured by Shin-Nakamura Chemical Industry Co., Ltd., methacryloyl equivalent: 628 g / eq.); M-230G: A compound having a methacryloyl group and a polyethylene oxide structure (M-230G manufactured by Shin-Nakamura Chemical Industry Co., Ltd., methacryloyl equivalent: 1068 g / eq.).
[0245] (G) Ingredients: PERHEXYL O: Free radical polymerization initiator (manufactured by Nippon Oil Company, "PERHEXYL (registered trademark) O").
[0246] (H) component: Polyether polyol A: Polyether polyol resin A containing hydroxyl terminals of an aliphatic backbone, manufactured in Example 6. Number average molecular weight 9000; L-64: Polyoxyethylene polyoxypropylene glycol (L-64 manufactured by ADEKA); KF-6012: Polyoxyalkylene modified silicone resin (Shin-Etsu Chemical Industry Co., Ltd., "KF-6012", viscosity (25℃): 1500 mmHg) 2 / s).
[0247] [Table 1] [Table 1. Resin Compositions of Examples and Comparative Examples]
[0248] [Evaluation test using the first specific composition (negative photosensitive resin composition)] (Formation of the experimental layer) On a 12-inch silicon wafer, the resin compositions obtained in the various examples and comparative examples were molded by compression molding under conditions of 130°C, 6 MPa, and 10 minutes of curing time to obtain a layer of resin composition with a thickness of 300 μm. The layer of resin composition was then thermo-cured at 150°C for 1 hour to obtain a cured sample as a layer formed from the cured resin composition. The obtained cured sample was ground 30 μm in the thickness direction using a grinding mill (DISCO "DAG810") to form a ground surface with an arithmetic mean roughness in the range of 10 nm to 300 nm.
[0249] The cured sample was cut into 4-inch circles along with the wafer. The first specific composition obtained in Example 3 was spin-coated onto the polished surface using a spin coater (MIKASA MS-A150). The spin-coating speed was set to a maximum speed range of 1000 rpm to 3000 rpm, ensuring a test layer of the desired thickness after heat curing. A pre-baking treatment at 120°C for 5 minutes was then performed on a hot plate to form a 10 μm thick layer of the first specific composition in the center of the polished surface. Finally, the layer of the first specific composition was subjected to a full cure treatment at 250°C for 2 hours to obtain a test layer with a central thickness of 8 μm.
[0250] (Determination of arithmetic mean surface roughness Ra) The arithmetic mean roughness Ra of the surface of the test layer opposite to the polished surface was measured using a non-contact surface roughness meter (Veeco Instruments "WYKO NT3300"). The measurement was performed in VSI mode with a 50x lens, and the measurement range was set to 121 μm × 92 μm. The arithmetic mean roughness Ra was measured at 10 locations on the test layer surface, and the average value was used.
[0251] (Measurement of TTV) The thickness of the test layer was measured at 15 measurement points, including the central and end portions of the wafer. The TTV of the test layer was calculated as the difference between the maximum and minimum measured thicknesses.
[0252] [Evaluation test using a second specific composition (positive photosensitive resin composition)] Except for using the second specific composition obtained in Manufacturing Example 5 instead of the first specific composition, the test layer was formed by the same method as described in the [Evaluation Test Using the First Specific Composition (Negative Photosensitive Resin Composition)], the arithmetic mean roughness Ra of the surface of the test layer opposite to the polished surface was measured, and the TTV of the test layer was measured.
[0253] [Determination of the wettability of cured resin compositions] The test layers manufactured in the aforementioned [evaluation test using the first specific composition (negative photosensitive resin composition)] and [evaluation test using the second specific composition (positive photosensitive resin composition)] were used as mirrors to observe the light bulb. Specifically, the light bulb was reflected onto the surface of the test layer, and the reflection of the light bulb on the surface was observed with the naked eye. If the outline of the observed light bulb image is clear, it indicates that the surface shape of the test layer is smooth and the thickness of the test layer is uniform. Furthermore, if the outline of the observed light bulb image is unclear, it indicates that the surface shape of the test layer is uneven and the thickness of the test layer is uneven. Therefore, based on the observed light bulb image, the wettability was evaluated according to the following criteria. "◎": The outline of the light bulb reflected on the surface of the test layer can be clearly seen and confirmed; “○”: The outline of the light bulb reflected on the surface of the test layer can be visually confirmed, but it is not clear; "×": The outline of the light bulb reflected on the surface of the test layer cannot be visually confirmed.
[0254] Evaluation of the toughness of the cured resin composition The resin compositions obtained in the various examples and comparative examples were thermocured in a thermal cycling oven at 150°C for 60 minutes to obtain resin boards with a thickness of 6 mm. Using the obtained resin boards, fracture toughness tests were performed using the CT specimen method according to ASTM E399-90 to determine the K1C value. Five samples were tested at a test speed of 1 mm / min (crosshead speed), a temperature of 23°C, and 48% RH, and the average value was obtained. This average value was 1.5 MPa·m. 1 / 2 The above situation is rated as "0"; the average value is 1.0 MPa·m. 1 / 2 Above and less than 1.5 MPa·m 1 / 2 The situation is evaluated as "△"; the average value is less than 1.0 MPa·m 1 / 2 The evaluation for this situation is "×".
[0255] [Determination of surface free energy of cured resin compositions] On a 12-inch silicon wafer that has undergone demolding, the resin compositions obtained in the various examples and comparative examples were molded by compression molding under conditions of 130°C, 6 MPa, and 10 minutes of curing time, resulting in a resin composition layer with a thickness of 300 μm. This resin composition layer was then thermo-cured at 150°C for 1 hour to obtain a cured layer formed from the cured resin composition. The resulting cured layer was ground to a thickness of 30 μm using a grinding mill (DISCO DAG810) to form a ground surface with an arithmetic mean roughness in the range of 10 nm to 300 nm. The cured layer was then cut together with the wafer into 2 cm squares to obtain samples.
[0256] For the polished surface of the cured layer of the above samples, the surface free energy based on Kitasaki Hata's theory was measured using a measuring device (DropMaster DMs-401, Kyowa Interface Science Co., Ltd.). Specifically, the contact angles of liquids (water, diiodomethane, and n-hexadecane) with the polished surface were measured, and the surface free energy of the polished surface was calculated based on Kitasaki Hata's theory from those measured contact angles. The contact angles were measured using the θ / 2 method. Furthermore, the contact angle measurements were performed 1 minute after the liquid droplet came into contact with the polished surface, which served as the measurement surface.
[0257] [Method for determining the elastic modulus of cured resin compositions] On a 12-inch silicon wafer that has undergone demolding, the resin compositions obtained in the various examples and comparative examples were molded by compression molding at a temperature of 130°C, a pressure of 6 MPa, and a curing time of 10 minutes to obtain a layer of resin composition with a thickness of 300 μm. This layer of resin composition was then thermo-cured at 150°C for 1 hour to obtain a cured resin composition. After the wafer was peeled off, three dumbbell-shaped test pieces (shape 1) were cut from the cured material. Subsequently, for each test piece, a tensile test was performed using an Orientec RTC-1250A tensile testing machine at 25°C in a laboratory environment to determine the elastic modulus (GPa) at 25°C. The measurement was performed according to JIS K7127:1999. The average value of the measured elastic modulus at 25°C for the three test pieces was calculated.
[0258] [Resolution Evaluation Experiment] (Preparation of the evaluation substrate) On a 12-inch silicon wafer, the resin compositions obtained in the various examples and comparative examples were molded by compression molding under conditions of 130°C, 6 MPa, and 10 minutes of curing time to obtain a layer of resin composition with a thickness of 300 μm. This layer of resin composition was then thermo-cured at 150°C for 1 hour to obtain a cured layer formed from the cured resin composition. The resulting cured layer was ground 30 μm in the thickness direction using a grinding mill (DISCO "DAG810") to form a ground surface with an arithmetic mean roughness in the range of 10 nm to 300 nm. The cured layer was then cut together with the wafer into 4-inch circles to obtain an evaluation substrate having a cured layer with a ground surface.
[0259] (Evaluation of resolution when using the first specific composition as a negative photosensitive resin composition) On the polished surface of the evaluation substrate, the first specific composition manufactured in Example 3 of the negative photosensitive resin composition was spin-coated using a spin coater (MIKASA MS-A150) at a maximum speed of 1500 rpm. Then, a pre-baking treatment was performed by heating on a hot plate at 120°C for 5 minutes to form a layer of negative photosensitive resin composition with a thickness of 10 μm on the polished surface.
[0260] The layer of the negative photosensitive resin composition is exposed through a mask having multiple circular light-shielding portions with a diameter of 10 μm. Exposure is performed using a patterning apparatus (UX-2240, manufactured by Ushio Electric Co., Ltd.) with i-rays (i-lines) at 300 mJ / cm². 2 The energy is then applied. Next, cyclopentanone is used for spray development, followed by rinsing with propylene glycol methyl ether acetate. When the exposure and development process allows for the formation of openings corresponding to all light-blocking portions on the layer of the negative photosensitive resin composition, the resolution is determined to be "○". Furthermore, if the surface shape or thickness of the spin-coated layer of the negative photosensitive resin composition is uneven, and residue remains at the openings corresponding to some or all of the light-blocking portions, the resolution is determined to be "×".
[0261] (Evaluation of resolution when using a negative photosensitive resin composition with a different composition than the first specific composition) On the polished surface of the evaluation substrate, the negative photosensitive resin composition N1 manufactured in Example 7 was spin-coated using a spin coater (MIKASA MS-A150) at a maximum speed of 1200 rpm. Then, a pre-baking treatment was performed by heating on a hot plate at 120°C for 5 minutes to form a layer of negative photosensitive resin composition with a thickness of 10 μm on the polished surface.
[0262] The layer of the negative photosensitive resin composition is exposed through a mask having multiple circular light-shielding portions with a diameter of 10 μm. Exposure is performed using i-rays at 200 mJ / cm² in a patterning apparatus (UX-2240, manufactured by Ushio Electric Co., Ltd.). 2 The energy is then used. Then, spray development is performed using a 2.38% TMAH aqueous solution, followed by rinsing with pure water. TMAH represents tetramethylammonium hydroxide.
[0263] When the exposure and development process described above forms openings corresponding to all light-blocking portions on the layer of the negative photosensitive resin composition, the resolution is determined to be "○". Furthermore, if the surface shape or thickness of the spin-coated layer of the negative photosensitive resin composition is uneven, and residue exists at the openings corresponding to some or all of the light-blocking portions, the resolution is determined to be "×". The evaluation results of the resolution using the negative photosensitive resin composition N1 are the same as those using the first specific composition in all examples and comparative examples. Therefore, it is confirmed that the evaluation results of the resolution using the first specific composition are also applicable to cases where a negative photosensitive resin composition having a different composition from the first specific composition is used.
[0264] (Evaluation of resolution when using a second specific composition as a positive-type photosensitive resin composition) On the polished surface of the evaluation substrate, a second specific composition manufactured in Example 5 of the positive photosensitive resin composition was spin-coated using a spin coater (MIKASA MS-A150) at a maximum speed of 1500 rpm. Then, a pre-baking treatment was performed by heating on a hot plate at 120°C for 5 minutes to form a layer of positive photosensitive resin composition with a thickness of 10 μm on the polished surface.
[0265] The layer of the positive photosensitive resin composition is exposed through a mask having multiple circular light-transmitting portions with a diameter of 10 μm. Exposure is performed using i-rays at 500 mJ / cm² in a patterning apparatus (UX-2240, manufactured by Ushio Electric Co., Ltd.). 2 The energy is applied. Then, spray development is performed using a 2.38% TMAH aqueous solution, followed by rinsing with pure water. When the exposure and development process allows openings corresponding to all light-transmitting areas to be formed on the layer of the positive photosensitive resin composition, the resolution is determined to be "○". Furthermore, if the surface shape or thickness of the spin-coated layer of the positive photosensitive resin composition is uneven, and residue remains at the openings corresponding to some or all of the light-transmitting areas, the resolution is determined to be "×".
[0266] (Evaluation of resolution when using a positive photosensitive resin composition with a different composition than the second specific composition) On the polished surface of the evaluation substrate, the positive photosensitive resin composition P1 manufactured in Example 8 was spin-coated using a spin coater (MIKASA MS-A150) at a maximum speed of 1500 rpm. Then, a pre-baking treatment was performed by heating on a hot plate at 120°C for 3 minutes to form a layer of positive photosensitive resin composition with a thickness of 10 μm on the polished surface.
[0267] The layer of the positive photosensitive resin composition is exposed through a mask having multiple circular light-transmitting portions with a diameter of 10 μm. Exposure is performed using i-rays at 500 mJ / cm² in a patterning apparatus (UX-2240, manufactured by Ushio Electric Co., Ltd.). 2 The energy was then used for spray development with a 2.38% TMAH aqueous solution, followed by rinsing with pure water.
[0268] When the exposure and development process described above forms openings corresponding to all light-transmitting portions on the layer of the positive photosensitive resin composition, the resolution is determined to be "○". Furthermore, if the surface shape or thickness of the spin-coated layer of the positive photosensitive resin composition is uneven, and residue exists at the openings corresponding to some or all of the light-transmitting portions, the resolution is determined to be "×". The evaluation results of the resolution using the positive photosensitive resin composition P1 are the same as those using the second specific composition in any of the examples and comparative examples. Therefore, it is confirmed that the evaluation results of the resolution using the second specific composition are also applicable to cases where a positive photosensitive resin composition with a different composition than the second specific composition is used.
[0269] [result] The results of the above-described embodiments and comparative examples are shown in the table below.
[0270] [Table 2] [Table 2. Results of the Examples and Comparative Examples]
[0271] [Explanation of Symbols] 1 Sample 10 Silicon wafers Surface of a 10U silicon wafer 20 Cured Samples Grinding surface of 20U cured sample 30 test layers Surface of 30U test layer 100 Semiconductor Chip Packaging 110 Semiconductor Chips 120 sealing layer 130 Rewiring Forming Layer 140 Rerouting Layer 150 solder mask layer 160 bump.
Claims
1. A resin composition comprising (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents and phenol-based curing agents, (C) an inorganic filler, and (D) a silane coupling agent. in, (A) The epoxy resin comprises one or more selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, glycidylamine type epoxy resin, alicyclic epoxy resin having an ester skeleton, epoxy resin having a butadiene structure, epoxy resin containing an oxidized olefin skeleton and a butadiene skeleton, epoxy resin containing a fluorene structure, and dicyclopentadiene type epoxy resin. (C) The cumulative particle size D50 of 50% of the inorganic filler material is greater than 0.2 μm and less than 15 μm; (C) 90% of the cumulative particle size D90 of the inorganic filler material is above 2μm and below 30μm; The amount of epoxy resin (A) is more than 1% by mass and less than 20% by mass relative to 100% by mass of the non-volatile components in the resin composition; (B) The amount of curing agent is 0.1% to 20% by mass relative to 100% by mass of the non-volatile components in the resin composition; The amount of (C) inorganic filler material is 60% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition; The amount of (D) silane coupling agent relative to 100% by mass of the non-volatile components in the resin composition is 0.01% by mass or more and 5.0% by mass or less; The cured product obtained by thermosetting the resin composition at 150°C for 1 hour has a strength of 25 mJ / m³. 2 The above surface free energy; In the case of an evaluation test in which a test layer was formed on the polished surface of a cured specimen of the resin composition using the test composition, The arithmetic mean roughness Ra of the surface of the test layer on the opposite side of the polished surface is greater than 10 nm and less than 500 nm. The difference between the maximum and minimum thickness of the test layer, TTV, is greater than 0.2 μm and less than 8 μm. The polished surface is formed by performing the following steps: A layer of the resin composition is formed on a silicon wafer by compression molding. The resin composition layer is thermally cured to obtain the cured sample, and The cured sample is ground to obtain the ground surface; The test layer is formed by performing the following steps: The cured sample was cut into a circle. The test composition is spin-coated onto the polished surface of the cured sample and heated to form a layer of the test composition. The test layer is obtained by thermally curing the layer of the test composition. The test composition is selected from at least one of negative photosensitive resin compositions and positive photosensitive resin compositions.
2. The resin composition according to claim 1, wherein, (A) Epoxy resins include naphthalene-type epoxy resins.
3. The resin composition according to claim 1, wherein, The amount of epoxy resin (A) is 3% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition.
4. The resin composition according to claim 1, wherein, The amount of epoxy resin (A) is less than 15% by mass relative to 100% by mass of the non-volatile components in the resin composition.
5. The resin composition according to claim 1, wherein, The amount of (B) curing agent is 2.0% by mass or more relative to 100% by mass of the non-volatile components in the resin composition.
6. The resin composition according to claim 1, wherein, (B) The amount of curing agent is less than 10% by mass relative to 100% by mass of the non-volatile components in the resin composition.
7. The resin composition according to claim 1, wherein, The amount of (C) inorganic filler material is 75% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition.
8. The resin composition according to claim 1, wherein, The amount of inorganic filler material is 95% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition.
9. The resin composition according to claim 1, wherein, The amount of inorganic filler material is 90% or less relative to 100% by mass of the non-volatile components in the resin composition.
10. The resin composition according to claim 1, wherein, The amount of (D) silane coupling agent is 0.10% by mass or more relative to 100% by mass of the non-volatile components in the resin composition.
11. The resin composition according to claim 1, wherein, The amount of (D) silane coupling agent is less than 0.5% by mass relative to 100% by mass of the non-volatile components in the resin composition.
12. The resin composition according to claim 1, wherein, The tensile modulus of the cured product obtained by thermosetting the resin composition at 150°C for 1 hour is less than 30 GPa.
13. The resin composition according to claim 1, wherein, The tensile modulus of the cured product obtained by thermosetting the resin composition at 150°C for 1 hour is less than 25 GPa.
14. The resin composition according to claim 1, wherein, The tensile modulus of the cured product obtained by thermosetting the resin composition at 150°C for 1 hour is 7 GPa or higher.
15. The resin composition according to claim 1, wherein, The tensile modulus of the cured product obtained by thermosetting the resin composition at 150°C for 1 hour is 9 GPa or higher.
16. The resin composition according to claim 1, used to form an insulating layer for semiconductor chip packaging.
17. The resin composition according to claim 1, wherein, In the evaluation test, the polished surface is formed by performing the following steps: A layer of the resin composition with a thickness of 300 μm was formed on a 12-inch silicon wafer by compression molding under conditions of 130°C, 6 MPa, and 10 minutes of curing time. The resin composition was heat-cured at 150°C for 1 hour to obtain the cured sample. The cured sample is ground to a thickness of 30 μm to obtain the ground surface with an arithmetic mean roughness of 10 nm to 300 nm.
18. The resin composition according to claim 1, wherein, In the evaluation test, the test layer is formed by performing the following steps: The cured sample was cut into a 4-inch circle. The test composition was spin-coated onto the polished surface of the cured sample and heated at 120°C for 5 minutes to form a layer of the test composition. The test composition was thermo-cured at 250°C for 2 hours to obtain the test layer with a central thickness of 8 μm.
19. The resin composition according to claim 1, wherein, The negative photosensitive resin composition is a composition with a viscosity of 35 poise obtained by dissolving 50 parts by weight of the first polymer, 50 parts by weight of the second polymer, 2 parts by weight of the compound shown in formula (1) below, 8 parts by weight of tetraethylene glycol dimethacrylate, 0.05 parts by weight of 2-nitroso-1-naphthol, 4 parts by weight of N-phenyldiethanolamine, 0.5 parts by weight of N-(3-(triethoxysilyl)propyl)o-carbamoylbenzoic acid, and 0.5 parts by weight of benzophenone-3,3'-bis(N-(3-triethoxysilyl)propionamide)-4,4'-dicarboxylic acid in a mixed solvent formed by N-methylpyrrolidone and ethyl lactate; the weight ratio of the mixed solvent is N-methylpyrrolidone:ethyl lactate = 8:2; The first polymer is a polymer with a weight-average molecular weight of 18,000 to 25,000. The first polymer is obtained by reacting 155.1 parts by mass of 4,4'-oxophthalic dianhydride and 134.0 parts by mass of 2-hydroxyethyl methacrylate with 206.3 parts by mass of dicyclohexylcarbodiimide, and further reacting with 93.0 parts by mass of 4,4'-diaminodiphenyl ether. The second polymer is a polymer with a weight-average molecular weight of 18,000 to 25,000. The second polymer is obtained by reacting 147.1 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 134.0 parts by mass of 2-hydroxyethyl methacrylate with 206.3 parts by mass of dicyclohexylcarbodiimide, and further reacting with 93.0 parts by mass of 4,4'-diaminodiphenyl ether. The positive photosensitive resin composition is a mixture of 100 parts by weight of the third polymer, 15 parts by weight of hexamethoxymethyl melamine, 11 parts by weight of 1-naphthoquinone-2-diazido-5-sulfonate, and 200 parts by weight of γ-butyrolactone. The third polymer is a polymer having a weight-average molecular weight of 10,000 to 50,000 and a dispersion of 2.
0. The third polymer is obtained by reacting 13.92 parts by mass of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane with 10.69 parts by mass of dodecanediol dichloride. 。 20. A cured product, which is a cured product of the resin composition according to any one of claims 1 to 19.
21. A resin sheet comprising: A support body, and a resin composition layer comprising the resin composition according to any one of claims 1 to 19 disposed on the support body.
22. A circuit board comprising a cured form of the resin composition according to any one of claims 1 to 19.
23. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 19.
24. A semiconductor device comprising the semiconductor chip package of claim 23.
25. A structure having: A cured layer formed from a cured thermosetting resin composition, and A layer of photosensitive resin composition formed in a manner that is in contact with the surface of a cured layer; The thermosetting resin composition comprises (A) an epoxy resin, (B) at least one curing agent selected from anhydride-based curing agents, amine-based curing agents and phenol-based curing agents, (C) an inorganic filler, and (D) a silane coupling agent; (A) The epoxy resin comprises one or more selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, glycidylamine type epoxy resin, alicyclic epoxy resin having an ester skeleton, epoxy resin having a butadiene structure, epoxy resin containing an oxidized olefin skeleton and a butadiene skeleton, epoxy resin containing a fluorene structure, and dicyclopentadiene type epoxy resin. (C) The cumulative particle size D50 of 50% of the inorganic filler material is greater than 0.2 μm and less than 15 μm; (C) 90% of the cumulative particle size D90 of the inorganic filler material is above 2μm and below 30μm; The amount of epoxy resin (A) is more than 1% by mass and less than 20% by mass relative to 100% by mass of the non-volatile components in the resin composition; (B) The amount of curing agent is 0.1% to 20% by mass relative to 100% by mass of the non-volatile components in the resin composition; The amount of (C) inorganic filler material is 60% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition; The amount of (D) silane coupling agent relative to 100% by mass of the non-volatile components in the resin composition is 0.01% by mass or more and 5.0% by mass or less; The cured product obtained by thermosetting the resin composition at 150°C for 1 hour has a strength of 25 mJ / m³. 2 The above surface free energy; The arithmetic mean roughness Ra of the surface of the layer opposite to the cured layer obtained by curing the photosensitive resin composition is greater than 10 nm and less than 500 nm. The difference between the maximum and minimum thickness (TTV) of the layer obtained by curing the photosensitive resin composition is 0.2 μm or more and 8 μm or less.
26. The structure according to claim 25, wherein, (A) Epoxy resins include naphthalene-type epoxy resins.
27. The structure according to claim 25, wherein, The amount of epoxy resin (A) is 3% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition.
28. The structure according to claim 25, wherein, The amount of epoxy resin (A) is less than 15% by mass relative to 100% by mass of the non-volatile components in the resin composition.
29. The structure according to claim 25, wherein, The amount of (B) curing agent is 2.0% by mass or more relative to 100% by mass of the non-volatile components in the resin composition.
30. The structure according to claim 25, wherein, (B) The amount of curing agent is less than 10% by mass relative to 100% by mass of the non-volatile components in the resin composition.
31. The structure according to claim 25, wherein, The amount of (C) inorganic filler material is 75% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition.
32. The structure according to claim 25, wherein, The amount of inorganic filler material is 95% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition.
33. The structure according to claim 25, wherein, The amount of inorganic filler material is 90% or less relative to 100% by mass of the non-volatile components in the resin composition.
34. The structure according to claim 25, wherein, The amount of (D) silane coupling agent is 0.10% by mass or more relative to 100% by mass of the non-volatile components in the resin composition.
35. The structure according to claim 25, wherein, The amount of (D) silane coupling agent is less than 0.5% by mass relative to 100% by mass of the non-volatile components in the resin composition.
Citation Information
Patent Citations
Polyamide-imide resin paste and coating film-forming material comprising the same
JP2004137370A
Semiconductor device and method of manufacturing semiconductor device
JP2012188555A
Epoxy resin molding material for sealing and semiconductor device using the same
JP2016074920A
Positive-type photosensitive resin composition
CN108604060A
Method for manufacturing printed wiring board
CN110035622A
